Changing thunderstorms environments in Saudi Arabia: Frequency, variability and drivers of change - Moutassem El Rafei; Andrew Dowdy; Mazen E. Assiri; Md. Arfan Ali; Muhammad Haroon Siddiqui; Sajjad Saeed; Saeed Ahmad Alghamdi; Shamsuddin Shahid (Atmospheric Research, 2026)

Unveiling the role of heat shock protein 83 (HSP83) in Gossypium hirsutum in enhancing whitefly stress tolerance - Muhammad Waseem Sajjad; Rubab Zahra Naqvi; Ifrah Imran; Mohammad Abubakar Yasin; Mariam Akhtar; Imran Amin (Molecular Genetics and Genomics, 2026)

Forecasting of murder crimes using classical and machine learning models - Ayesha Haider; Muhammad Ijaz; Fatimah Essa Almuhayfith; Randa Alharbi; Irum Sajjad Dar (Next Research, 2026)

Interfacial Stabilization and Geochemical Transformation of Antimony in Contaminated Soil Using a Ferrihydrite-Functionalized Biochar–Montmorillonite Composite - Rabia Safeer; Guijian Liu; Balal Yousaf; Aniqa Ashraf; Muhammad Irtaza Sajjad Haider; Samra Ijaz; Ruijia Liu (International Journal of Environmental Research, 2026)

Mud crab (Genus Scylla) aquaculture: integrating biological knowledge and technological advances toward sustainability - Murak; Muhammad Sajjad Ahmad; Hanafiah Fazhan; Kuo-Wei Lan; Khor Waiho; Hongyu Ma; Mhd Ikhwanuddin (Aquaculture International, 2026)

Improving groundwater level prediction based on optimized deep learning model with Coati algorithm - Rana Muhammad Adnan; Jing-Cheng Han; Mo Wang; Sandeep Samantaray; Abinash Sahoo; Sajjad Firas Abdulameer; Mohammad Al-Suwaiyan; Zaher Mundher Yaseen (Environmental Modelling & Software, 2026)

Atomic-scale Ni3Ti/CNT interface modulation enables fast electron transport for bifunctional water splitting and supercapacitors - Sayed Zafar Abbas; Dhanasekaran Vikraman; Zulfqar Ali Sheikh; Zeesham Abass; Jeung Choon Goak; Jongwan Jung; Hyun-Seok Kim; Muhammad Ali; Sajjad Hussain; Naesung Lee (Chemical Engineering Journal, 2026)

Evidence for Mg-rich fluids in the diagenesis and porosity evolution of the Sirban Dolomite, Hazara Basin, Pakistan - Asif Khan; Mumtaz Muhammad Shah; Sajjad Khan (Carbonates and Evaporites, 2026)

Dopamine Receptor D2 gene Polymorphisms rs2005313, rs4274224, and rs4938019 in Pakistani Patients with Schizophrenia:a Diagnostic Tool for Schizophrenia - Ishrat Yaseen; Saleem Ahmad; Muhammad Ghalib; Muhammad Shahbaz Aslam; Rabbia Tariq; Osheen Sajjad; Faisal Yaseen (Journal of Molecular Neuroscience, 2026)

An Innovative conceptual framework to identify the potential sites for rainwater harvesting in arid regions - Muhammad Shahid; Muhammad Waseem; Khalil Ur Rahman; Sajjad Haider; Hamza Farooq Gabriel (Environment, Development and Sustainability, 2026)

Redox homeostasis and trace metal regulation drive allantoin-induced tolerance against combined microplastic and cadmium stress in pea (Pisum sativum L.) - Anshra Murtaza; Muhammad Munir; Rizwan Rasheed; Muhammad Arslan Ashraf; Fakhar Abbas; Sarah Owdah Alomrani; Abdulrahman Alasmari; Shafaqat Ali; Sajjad Hassan Askari (Journal of Trace Elements in Medicine and Biology, 2026)

Engineered Adsorbents for Microplastic Mitigation: From Interfacial Mechanisms to Scalable Environmental Perspectives - Hammad Sajjad; Waleed Altaf; Ramika Javaid; Tehreem Fakhra; Muhammad Hayat; Ammar bin Yousaf; Nadeem Raza; Suryyia Manzoor; Lilia Basilio de Caland (Journal of Environmental Chemical Engineering, 2026)

Structure Guided Identification of Small Molecule Inhibitors Targeting Staphylococcus aureus α-Hemolysin - Saeed Ullah Khattak; Nida Raza; Mawahib Ahmed; Ayesha Saleem; Muhammad Salim; Sajjad Ahmad (Journal of Pharmaceutical Innovation, 2026)

Immunoinformatics-driven multi-epitope vaccine design as a promising strategy against multidrug-resistant pathogens: a comprehensive review - Rameen Nasir; Muhammad Mutayyab Javaid; Raheen Rahman; Rimsha Abbasi; Muneeb Khalid; Muhammad Arslan; Muhammad Amjad Sajjad; Ahsan Ibrahim (Folia Microbiologica, 2026)

Analyzing Household Biological Waste for Energy Efficiency: Advancement Towards Sustainable Energy - Dhaif Allah Ahmed Hadi; Jicheng Liu; Javed Akram; Shahid Ali; Song Yanan; Kathih Ahmed Ali Hadi; Muhammad Sajjad Hussain (Circular Economy and Sustainability, 2026)

Edaravone dexborneol in acute ischemic stroke: a systematic review and meta-analysis of randomized trials with clinical and thrombectomy-specific subgroup analyses - Eman Tariq; Hooriya Ahmed; Tayyaba Ikram Qazi; Abdul Muhaimin; Aleena Amir Malik; Javeria Soomro; Rahimeen Qureshi; Zainab Murtaza; Sarum Ali Khan; Wajeeha Komal; Hadia Tanveer; Rida Ameer; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Can baxdrostat redefine blood pressure control in resistant and uncontrolled hypertension? a systematic review, meta-analysis, and trial sequential analysis - Bilal Wazir Khan; Muhammad Yahya; Hamza Wazir Khan; Miguel Alejandro Rivas Perez; Tayyaba Ikram Qazi; Humaira Obaid; Muhammad Mustafa Khan; Muhammad Maaz Amjad; Muhammad Faaz Khan; Aneeq Mahmood Khan; Muhammad Junaid Khan; Sajjad Khan; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Transforming Banana Peel Waste into a Nano Biostimulant: Effects on Maize Seed Germination and Physio-Morphological Traits - Palwasha Sajjad; Umair Riaz; Azer Ahmadov; Tanveer-ul-Haq; Nazar Fareid; Faiza Hassan; Muhammad Adeel; Ayta Umar; Ren Maozhi; Muhammad Usman Aslam; Lamy Hamed (Journal of Plant Growth Regulation, 2026)

Spatiotemporal dynamics of historical and future drought conditions over the Arabian Peninsula from ERA5 and CMIP6 data - Muhammad Haroon Siddiqui; Mazen E Assiri; Sajjad Saeed; Md Arfan Ali; Moutassem El Rafei; Shahad Bahamdan; Abdullah Masoud Alqahtani; Abdulrahman AlHaidari; Abdulrahman Alsalhi; Ohood Alzahrani; Shamsuddin Shahid (Journal of Earth System Science, 2026)

Antimicrobial Plant Protein Patatin: Identification and In-Silico Analysis Through Phylogenetics and Molecular Docking - Sarah Tariq; Binish Khaliq; Hina Shaheen; Ahmad Riaz; Sumaira Rubbani; Muhammad Sajid Hamid Akash; Amjad Hussain; Muhammad Imran; Muhammad Arslan Javed; Ahmed Akrem; Sohaib Mehmood; Sajjad Azam (Agricultural Research, 2026)

Inter-device interaction effects on turbine performance and blade loads in axially aligned tidal turbine arrays - Mujahid Badshah; Saeed Badshah; Sajjad Ahmad; Imtiaz Alam Shah; Zia Ur Rehman; Muhammad Amjad; Sakhi Jan (Ocean Engineering, 2026)

Sustainable development of novel lime marble dust composite compressed earth blocks: mechanical and durability performance evaluation - Salman Farooq; Zia Ul Islam; Muhammad Isa Khan; Hamza Sajjad (Innovative Infrastructure Solutions, 2026)

GCMS, phytochemical analysis, biological potential of dichloromethane extract of Yucca elephantipes regel roots: in vitro and in silico studies - Muhammad Shoaib Khan; Mehreen Jabeen; Farhan Siddique; Sajjad Ahmad; Amna Aqdas; Umair Jillani; Yasir Zaman; Abdulrahman Alshammari; Norah A. Albekairi (Natural Product Research, 2026)

Beyond traditional water resources reliance: unlocking Pakistan’s national water harvesting potential via analysis of opportunities and risks - Junaid Ahmad; Muhammad Mohsin Leghari; Muhammad Sajjad (Environment, Development and Sustainability, 2026)

What drives coastal disaster resilience at the household level? deciphering coastal household-level economic, social, and infrastructure robustness (CHESIR) determinants - Sardar Al Imran; Muhammad Sajjad; Md. Nazmus Sadath (Environment, Development and Sustainability, 2026)
Coastal communities experience increasing threats from hazards under climate change, yet evidence on household-level disaster resilience remains fragmented, specifically in developing nations. We here propose Coastal Household-level Economic, Social, and Infrastructure Robustness (CHESIR) indicators utilizing data on household survey ( n = 441 households) in two coastal hazards-exposed unions in southwestern Bangladesh (September–November 2023). An ordered logistic regression model is developed to detect significant CHESIR indicators related to household resilience. Of 22 indicators measured, 64% appear to be significant in Koilasganj and 68% in Laudubi ( p < .05). Nine indicators were significant determinants in both unions, including emergency fund (OR = 8.21; 95% CI: 3.56–18.94), savings fund (OR = 8.64; 4.67–15.97), accessibility to sufficient food (OR = 6.06; 3.11–11.79), diversification of livelihoods (OR = 9.25; 5.04–16.98), accessibility to disaster information centers (OR = 8.10; 4.29–15.27), participation in NGO programs (OR = 4.73; 2.63–8.51), accessibility to tube-wells (OR = 4.66; 2.52–8.64), semi-brick housing (OR = 28.61; 11.46–71.45), and accessibility to nearby river/forest resources (OR = 6.36; 3.39–11.93). As the evaluation relies on cross-sectional survey data, the anticipated odds ratios exhibit statistical associations rather than causal effects. These outcomes highlight household-level actionable leverage points to strengthen resilience in coastal Bangladesh and put forth a transferable assessment framework for similar risk contexts.

Influence of inter-device spacing on performance and blade loads in staggered arrays of tidal current turbines - Mujahid Badshah; Saeed Badshah; Zia Ur Rehman; Sajjad Ahmad; Muhammad Amjad; Sakhi Jan; Imtiaz Alam Shah (Ocean Engineering, 2026)

Parametric optimization and mechanistic investigation of polyvinyl chloride microplastic degradation via an intensified hydrothermal Fenton reaction - Muhammad Zeeshan Gulzar; Guijian Liu; Muhammad Imran; Muhammad Arif; Samina Irshad; Bisma Sattar; Muhammad Irtaza Sajjad Haider; Huihui Zhou; Balal Yousaf (Journal of Water Process Engineering, 2026)

Paleocene stratigraphic framework and sedimentary architecture in the Sub-Himalayan Fold and Thrust Belt of Muzaffarabad, Pakistan: Depositional environment, Biotas, Paleogeographic and Economic Significance - Syed Kamran Ali; Arslan Sajjad; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Ahmer Bilal; Aamir Asghar; Aijaz Ali Halepoto; Evangelia Besiou; Assimina Antonarakou (Journal of Sedimentary Environments, 2026)

Disaster management technology and approaches: a focus on heterogeneous systems - Muhammad Haris; Sajjad Keshtkar; Adeel Anjum; Madiha Haider Syed; Hirohisa Kojima; Rafiq Ahmad (Environment Systems and Decisions, 2026)

Boosting Sustainability: Integrating Green Practices With the Circular Economy - Abdul Rehman; Muhammad Ibrahim Shahid; Sajjad Ahmad Baig; Fariha Fatima (Circular Economy and Sustainability, 2026)

Heat and humidity stress aggravate high-fat diet-induced kidney damage in albino rats - Muhammad Mubashar Shaukat; Robina Shaukat; Shaaf Ahmad; Nabila Roohi; Sajjad-Ur-Rahman (Biologia Futura, 2026)

Biochemical and histological alterations in the liver of albino rats fed a carbohydrate-rich diet under chronic heat and humidity stress - Robina Shaukat; Muhammad Mubashar Shaukat; Shaaf Ahmad; Nabila Roohi; Sajjad-Ur-Rahman (Biologia Futura, 2026)

Identification and Computational Analysis of a Novel Pathogenic DKC1 Variant Underlying X-Linked Dyskeratosis Congenita - Namra Asghar; Wardah Sajjad; Muhammad Naeem (Biochemical Genetics, 2026)

Phylogenetic and genome-wide analysis of codon usage reveals geographic and host-specific adaptation in Vaccinia virus - Hafsa Iqbal; Faisal Ahmad; Sajjad Ahmad; Iftikhar Ahmad; Muhammad Yar Sobhan Qadir; Ali Khalid; Zurva Ashraf; Zohra Ahmad; Ferjeni Zouidi (Archives of Virology, 2026)

Mechanistic and Data-Guided Design of Biochar Adsorbents for Gas Phase Pollution Control: A State-of-the-Art Review - Hammad Khan; Muhammad Arshad; Ahsan Jalal; Ubaid Khalid; Arslan Maqbool; Mahvash Ansari; Sajjad Hussain (Environmental Science and Pollution Research, 2026)

Pangenome-assisted characterization of TaBAM genes and association of TaBAM16-1B with NDVI in wheat - Maira Anam; Zulqurnain Khan; Muhammad Ali Sher; Muhammad Sajjad; Muhammad Kashif Naeem; Zijin Zhang; Sania Javeed; Fatima Javeria; Jing Chen; Shoaib Ur Rehman (Theoretical and Applied Genetics, 2026)

Synergistic photo-assisted AOPs using acid-modified biochar: Enhanced micropollutant levofloxacin degradation in industrial wastewater - Muhammad Irtaza Sajjad Haider; Guijian Liu; Balal Yousaf; Muhammad Arif; Kiran Aziz; Bisma Sattar; Muhammad Zeeshan Gulzar; Hameer Chand; Ruijia Liu (Desalination, 2026)

Multiscale mechanistic study into cellulose pyrolysis and Co-pyrolysis with polyethylene via ReaxFF molecular dynamics and experimental validation - Yu Zhang; Muhammad Sajjad Ahmad; Wenjun Zhou; Yingna Li; Rongpu Cao; Boxiong Shen (Chemical Engineering Journal, 2026)

Unraveling oak diversity: molecular characterization and phylogenetic relationships of Quercus species from the western Himalayas - Ayesha Azeem; Daniel Potter; Abdul Majid; Sajjad Sajjad; Khushi Muhammad; Irfan Ullah; Asif Khan; Abdulwahed Fahad Alrefaei; Sajid Ali (Plant Systematics and Evolution, 2026)

Remote sensing-based 2D hydrodynamic modeling and assessment of the 2014 flood in the Jhelum river basin - Rizwan Mansha; Sajjad Haider; Muhammad Azmat; Hamza Farooq Gabriel; Fahim Ullah (Modeling Earth Systems and Environment, 2026)

Unlocking the Functional Dynamics of ERF013 in Arabidopsis thaliana: A Key Player in Plant Growth Regulation - Rahmatullah Jan; Lubna; Saleem Asif; Zakirullah Khan; Muhammad Farooq; Eman R. Elsharkawy; Sajjad Asaf; Kyung-Min Kim (Journal of Plant Growth Regulation, 2026)

Emerging challenges and sustainability pathways in global aquaculture of mud crab (genus Scylla) - Murak; Khor Waiho; Hanafiah Fazhan; Muhammad Sajjad Ahmad; Kuo-Wei Lan; Hongyu Ma; Mhd Ikhwanuddin (Aquaculture International, 2026)

Insecticidal activity against mosquito larvae, leishmanicidal activity, and cytotoxicity against human cells of a synthesized thiourea compound and a column chromatography fraction (AF5) from the n-hexane soluble fraction of Artemisia scoparia - Mirza Gul; Muhammad Zahid; Hazrat Ali; Muhammad Said; Sajjad Ahmad (Journal of Asia-Pacific Entomology, 2026)

Fabrication, Characterization, and Effects of CuS Nanoparticles as Nano-Fertilizers on the Morphological, Biochemical Responses, and Bioaccumulation of Metal in Soybean (Glycine Max L.) and Sesame (Sesamum Indicum L.) - Jehangir Khan; Anila Sajjad; Khalid Khan; Ihsan Ullah; Syed Hamza Safeer; Muhammad Zia (Journal of Soil Science and Plant Nutrition, 2026)

Potential efficacy of insecticides and plant growth regulators against Oxycarenus hyalinipennis (Costa) during the fruiting stage of cotton (Gossypium hirsutum L.) - Muhammad Saqib Ajmal; Muhammad Farhan; Sajjad Ali; Qaiser Shakeel; Habib Ali; Ammara Riaz; Javaid Iqbal; Konul Ahmadova; Muhammad Sarmad; Muhammad Sajjad (International Journal of Tropical Insect Science, 2026)

Synthesis of quinoline-pyridazinone hybrid molecules by using a bio-based aldo-X building block DMEMPO from levulinic acid - Muhammad Noman Haider Tariq; Gul Khanda Sajjad; Tianjian Zhang; Rongxian Bai; Babak Kaboudin; Yanlong Gu (Sustainable Chemistry and Pharmacy, 2026)

Retraction notice to “Highly antifouling polymer-nanoparticle-nanoparticle/polymer hybrid membranes” [Sci. Total Environ. 810 (2022) / 152228] - Vahid Vatanpour; Maryam Jouyandeh; Seyed Soroush Mousavi Khadem; Shadi Paziresh; Ahmad Dehqan; Mohammad Reza Ganjali; Hiresh Moradi; Somayeh Mirsadeghi; Alireza Badiei; Muhammad Tajammal Munir; Ahmad Mohaddespour; Navid Rabiee; et al. (Science of The Total Environment, 2026)

Competitive adsorption of antibiotics on waste-derived hybrid biochar: Performance, mechanism, and life cycle assessment - Ali Hamid; Ahsan Jalal; Muhammad Arshad; Muhammad Usama; Sajjad Hussain; Hammad Khan (Journal of Environmental Chemical Engineering, 2026)

Synergistic effects in FeP4-NPC-CP Nanocomposites electrocatalysts for Boosted nitrate reduction to ammonia - Ya-Fei Guo; Sajid Mahmood; Anum Bilal; Ali Bahadur; Shahid Iqbal; Ali Hussain; Muhammad Sajjad; Syed Kashif Ali; Salah Knani (Fuel, 2026)

Genome-wide identification of RCC1 gene family in pepper (Capsicum annuum L.) and functional analysis of CaRCC1-16 under heat stress - Nadia Sajjad; Tayeb Muhammad; Altaf Hussain; Yong Kang; Qiaomin Yang; Mahnoor Khattak; Minghui Lu (Plant Cell Reports, 2026)

Effect of CuS NPs on growth, productivity, and biochemical characteristics and oil profile of Sesamum indicum L. under field trials - Jehangir Khan; Ihsan Ullah; Anila Sajjad; Muhammad Zia (Journal of Crop Science and Biotechnology, 2026)

Quantifying key drivers of atmospheric methane across Pakistan using a machine learning approach - Farzana Altaf; Toqeer Muhammad; Shahid Nadeem; Asif Sajjad; Mazhar Iqbal (Environmental Monitoring and Assessment, 2026)

Rift Valley fever in Mauritania and Senegal: A One Health imperative - Muhammad Abdullah Ali; Zaryab Bacha; Fatima Sajjad (Infectious Diseases, 2026)

Retraction notice to “Almond shell-derived biochar decreased toxic metals bioavailability and uptake by tomato and enhanced the antioxidant system and microbial community” [Sci. Total Environ. 929 (2024) 172632] - Muhammad Imran Ghani; Mohammad Abass Ahanger; Tanveer Ali Sial; Sajjad Haider; Junaid Ali Siddique; Ruidong Fan; Yanjiang Liu; Esmat F. Ali; Manish Kumar; Xing Yang; Jörg Rinklebe; Xiaoyulong Chen; et al. (Science of The Total Environment, 2026)

Electron-rich sulfur sites and dual interfacial bonds in S-scheme heterojunction enable high quantum yield and stable hydrogen production - Sharafat Ali; Sajjad Ali; Shu-Long Li; Ahmed Ismail; Sher Ali; Pir Muhammad Ismail; Syed Ul Hasnain Bakhtiar; Fazal Raziq; Mohammad Z. Rahman; Liang Qiao (Chemical Engineering Journal, 2026)

Extended reduced versus full-dose treatment with factor Xa inhibitors in patients with venous thromboembolism: a GRADE-assessed systematic review and meta-analysis of randomized controlled trials - Umama Alam; Muhammad Abdullah Ali; Muhammad Ansab; Shree Rath; Fazia Khattak; Zaryab Bacha; Hafiza Tooba Siddiqui; Fatima Sajjad; Abdullah Afridi; Zarar Ahmad Khan Afridi; Osama Ahmad; Abdul Moiz; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Genetic Innovations in Soybean: Key Genes Driving Salinity Tolerance - Muhammad Hafeez Ullah Khan; Jabar Zaman Khan Khattak; Ali Muhammad; Ehsan Ali; Sajjad Ali; Shah Fahad; Xianzhong Feng (Journal of Plant Growth Regulation, 2026)

Integrated assessment of groundwater potential and quality in a seismically active Himalayan city: a case study from Muzaffarabad, Pakistan - Raja Dilawar Sajjad; Abrar Niaz; Ahmer Bilal; Muhammad Tayyib Riaz; Ali Yousaf Khan; Xiwu Luan (Environmental Geochemistry and Health, 2026)

Microbial Dream Team: Cotton Performs Better in Salty Soil with Pseudomonas hunanensis RT-12 and Staphylococcus caprae DS-2 - Abid Ullah; Sajjad Ahmad; Muhammad Atif Azeem; Shariat Ullah; Sami Ullah; Muhammad Laiq; Asma Shah; Hua Shao (Current Microbiology, 2026)

Green Practices, knowledge processes and women’s business performance in Pakistan’s manufacturing sector - Said Muhammad; Yin Zhichao; Sajjad Alam; Naveed Khan (Environment, Development and Sustainability, 2025)

Synthesis of nano-ferrites-based materials: A new paradigm for electrochemical sensors - Sajjad Hussain; Imamdin Chandio; Md Abdur Rashid; Imran Sadiq; Jameel Ahmed Baig; Shakoor Ahmed Solangi; Muhammad Shahbaz; Khalid Hussain Thebo (Journal of Environmental Chemical Engineering, 2025)

Innovative Fe-F-Co-doped NiO nanoarrays: Pioneering high-efficiency electrochemical nitrate reduction to ammonia - Anum Bilal; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Ibrahim Khan; Imran Mahmood Khan; Muhammad Sajjad; Shahid Ali; Nicholas M. Musyoka; Guocong Liu; Abd-ElAziem Farouk; Nouf M. Alyami (Journal of Environmental Chemical Engineering, 2025)

Sustainable biodiesel production via Alkanna tinctoria oil Conversion: A multi-method modeling approach utilizing crab shell-derived biochar catalysts - Ali Hamid; Hammad Khan; Arsalan Arif; Muhammad Arshad; Sajjad Hussain; Arslan Maqbool (Biomass and Bioenergy, 2025)

Hybrid ensembled machine learning algorithm for landslide susceptibility assessment and data enhancement via Dual Discriminator Conditional Generative Adversarial Network - Sajid Hussain; Bin Pan; Wajid Hussain; Meer Muhammad Sajjad; Muhammad Ali; Zeeshan Afzal; Rebouh Nazih Yacer; Aqil Tariq (Natural Hazards, 2025)

Halotolerant Bacillus Aryabhattai Strain PM34 Mitigates Salinity Stress and Enhances the Physiology and Growth of Maize - Muhammad Atif Azeem; Salman Khan; Fawad Ali; Sajjad Ahmad; Gul Rahim; Muhammad Iftikhar; Majid Iqbal; Rawa Saad Aljaloud; Khaloud Mohammed Alarjani; Hassan Javed Chaudhary (Journal of Plant Growth Regulation, 2025)

Consortium of Endophytic Bacillus australimaris CK11 and Staphylococcus epidermidis CK9 from Commiphora gileadensis Mediates Tomato Resilience to Combined Salinity, Heat, and Drought Stresses - Syed Saad Jan; Nasir Ali Khan; Sajjad Asaf; Raheem Shahzad; Lubna; Muhammad Imran; Saqib Bilal; In-Jung Lee; Ahmed Al-Harrasi (Journal of Plant Growth Regulation, 2025)

Effect of a carbohydrate-rich diet on kidney ultrastructure in albino rats exposed to heat and humidity stress - Robina Shaukat; Muhammad Mubashar Shaukat; Husna Ahmad; Nabila Roohi; Sajjad-ur -Rahman; Rifat Ullah Khan (International Journal of Biometeorology, 2025)

Switching on survival: how rice outsmarts heat with a natural gene circuit - Mohammad Abubakar Yasin; Muhammad Waseem Sajjad; Rubab Zahra Naqvi; Imran Amin; Muhammad Arif (Functional & Integrative Genomics, 2025)

QBEmax redefines the precise base editing in crop plants - Muhammad Waseem Sajjad; Fatima Muzamil; Rubab Zahra Naqvi; Imran Amin (Functional & Integrative Genomics, 2025)

AZD7648 (DNA-PKcs inhibitor): a two-edged sword for editing genomes - Muhammad Waseem Sajjad; Ifrah Imran; Fatima Muzamil; Rubab Zahra Naqvi; Imran Amin (Functional & Integrative Genomics, 2025)

Microfacies analysis and depositional environment of Eocene Chorgali formation at Khanpur Dam Road Section, Hazara Basin, Pakistan - Bilal Shah; Syed Mamoon Siyar; Salman Khurshid; Dicky Muslim; Raden Irvan Sophian; Zahid Ullah; Abdul Wahid Asykarulloh; Asad Muhammad; Syed Muhammad; Wasim Sajjad (Carbonates and Evaporites, 2025)

Comprehensive study on efficient diclofenac sodium removal using walnut and pistachio shell activated carbon: ANN, kinetics, isotherms, thermodynamics and DFT calculations - Sinem Temiz Seymen; Handan Atalay Eroğlu; Elif Nihan Kadıoğlu; Muhammad Umar; Ali Hamid; Hammad Khan; Sajjad Hussain; Feryal Akbal (Biomass and Bioenergy, 2025)

Emission characteristics of a compression ignition engine using biodiesel and clove oil antioxidant blends - Sher Muhammad Ghotto; Sajjad Bhangwar; Ramez Raja; Muhammad Kashif Abbasi; Gordhan Das Valasai; Muhammad Ramzan Luhur; Stefano Landini (Biomass and Bioenergy, 2025)

Modeling the impact of climate warming on tomato phenology - Shakeel Ahmad; Ghulam Abbas; Zartash Fatima; Sajjad Hussain; Muhammad Ali Khan; Mukhtar Ahmed; Carol Jo Wilkerson; Gerrit Hoogenboom (Agricultural and Forest Meteorology, 2025)

Modelling pandemic-induced spatially heterogeneous patterns in income shock, food insecurity and their driving factors: a case of Pakistan - Muhammad Sajjad; Syed Hassan Raza; Wajiha Haq; Syeda Fatima Rubab (Environment, Development and Sustainability, 2025)
While pandemic-related income shock (IS) compromises societal well-being by leading to food insecurity (FI) in developing countries, evaluating the spatial inequities of IS, FI, and their significant driving factors is imperative for informed and targeted interventions. In this context, we explore spatial disparities in IS and FI, model significant factors driving IS, and examine the potential association between FI and IS in Pakistan—a nation with ~ 255 million people and vulnerable to food crises—using Covid-19 as a case study. Through the integrated deployment of spatial, econometric, and statistical models, priority intervention areas for IS and FI are identified, enabling efficient resource allocation and informed decision-making. Furthermore, spatial relationships among IS, FI, and significant factors are visualized using bivariate mapping to provide a geographical perspective, supporting the formulation of evidence-based action plans to mitigate their impacts. Our results show that Balochistan, the least developed province of Pakistan, is likely to observe higher levels of IS (95% confidence) during pandemics. Asset ownership, illiteracy, and employment are among the significant factors that drive IS in Pakistan. The geographical evaluation reveals considerable spatial heterogeneity in IS, FI, and several associated factors across the study area. While the higher IS clusters are identified in Khyber Pakhtunkhwa, the hotspots of FI are evident in Sindh province (95% confidence). This study has practical implications for medium- to long-term policy responses to health emergencies, which are essential for building resilience against future pandemics.

From space to screen: Recent advances in remote sensing for mangrove valuation through a bibliometric lens - Sum Yee Luk; Muhammad Sajjad (Ocean & Coastal Management, 2025)

Towards greening smart cities: Navigating net zero carbon in construction by 2050 through sustainable practices, innovation climate, and management support - Muhammad Javid Nawaz; Aymen Sajjad; Abdul Haseeb Tahir; Muhammad Adnan; Muhammad Umer; Huaming Song (Sustainable Cities and Society, 2025)

Functionalized biochar with enhanced interfacial properties for synergistic adsorption and photodegradation mechanisms of levofloxacin in industrial effluents - Muhammad Irtaza Sajjad Haider; Guijian Liu; Balal Yousaf; Muhammad Arif; Aniqa Ashraf; Rabia Safeer; Samra Ijaz; Ruijia Liu (Process Safety and Environmental Protection, 2025)

Sustainable wastewater treatment via nitrogen/sulfur co-doped graphene composite: Mechanistic insights & process optimization - Humaira Seema; Muhammad Arshad; Arslan Maqbool; Sumbal Zeb; Ali Hamid; Muhammad Umar; Sajjad Hussain; Hammad Khan (Journal of Water Process Engineering, 2025)

Tailoring the local environment of biochar by synergistic effects of AuPd alloy for enhanced catalytic wet air oxidation of formaldehyde - Sajid Ali; Kok Bing Tan; Kaiji Xu; Songbo Chen; Muhammad Ubaid Ali; Amad Arshad; Shafqat Ullah; Shamaila Sajjad; Andriambinintsoa Ranaivoson Tojonirina; Guowu Zhan (Journal of Environmental Chemical Engineering, 2025)

Paleoenvironmental conditions and key drivers of organic matter accumulation in the early cretaceous Talhar Shale, Lower Indus Basin, Pakistan - Rizwan Sarwar Awan; Bo Liu; Qamar Yasin; David A. Wood; Hamad ur Rahim; Muhammad Amar Gul; Sajjad Ali; Khawaja Hasnain Iltaf; Ashar Khan (Journal of Asian Earth Sciences, 2025)

Bimetallic metal-organic frameworks as versatile electrocatalysts for water splitting in neutral and alkaline environments - Syed Arfan Haider; Tehseen Mushtaq; Bakhtawar Sajjad; Munazza Shahid; Muhammad Altaf; Ayman Nafady; Ghayoor Abbas Chotana; Manzar Sohail; Shahid Rasul; Raja Shahid Ashraf (Fuel, 2025)

Monochalcogenide-based retina-inspired photosynapses for energy-efficient neuromorphic computing and artificial visual system application - Muhammad Riaz; Zeesham Abbas; Jiayi Li; Syed Khizar Abbas Abidi; Muhammad Hussain; Syed Hassan Abbas Jaffery; Muhammad Suleman; Haider Abbas; Diing Shenp Ang; Sajjad Hussain; Jongwan Jung (Chemical Engineering Journal, 2025)

Liver response to heat and humidity stress in high fat diet fed rats: a biochemical and histological investigation - Muhammad Mubashar Shaukat; Robina Shaukat; Shaaf Ahmad; Nabila Roohi; Sajjad ur Rahman; Mikhlid H. Almutairi; Abdulwahed Fahad Alrefaei; Rifat Ullah Khan; Sifa Dai (International Journal of Biometeorology, 2025)

Exploring the diversity and ethnomedicinal uses of wild edible plants in District Poonch, Azad Jammu and Kashmir - Amna Mustafa; Ansar Mehmood; Khawaja Shafique Ahmad; Sajjad Hussain; Muhammad Faraz Khan; Mushtaq Ahmad (Genetic Resources and Crop Evolution, 2025)

Enzymatic responses of fish (Ctenopharyngodon idella) exposed to lethal concentrations of selected trace metals - Nazish Shah; Muhammad Khisroon; Said Sajjad Ali Shah; Abdur Rahim (Environmental Geochemistry and Health, 2025)

Integrated PSInSAR and SBAS-InSAR analysis for landslide detection and monitoring - Sajid Hussain; Bin Pan; Wajid Hussain; Meer Muhammad Sajjad; Muhammad Ali; Zeeshan Afzal; M. Abdullah-Al-Wadud; Aqil Tariq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Recent advances in beta-type hexagonal ferrites: Synthesis, structural, vibrational and electromagnetic characteristics - M. Irfan; Shafaq Waqar; Hafiz Ghulam Shabbir; Tehreem Idrees; Fatima Khan; Komel Maryam; Maryam Choudhary; Isbah Shamshad; Abdul Rehman Ashiq; Shagufta Gulbadan; Muhammad Azhar Khan; Nayyab Sajjad (Next Research, 2025)

Threading future biotech crops with microneedles - Rubab Zahra Naqvi; Muhammad Waseem Sajjad; Imran Amin (Molecular Plant, 2025)

Evaluating the cooling potential of urban green spaces in Faisalabad integrating invest urban cooling model with multisource remote sensing data - Hafiz Abdul Basit Zaid; Usman Mahmood Mughal; Muhammad Amin; Meer Muhammad Sajjad; Muhammad Farhan; Amir Sattar; Shujaat Ali; Mujtaba Ali; Qurat ul Ain (Theoretical and Applied Climatology, 2025)

Unlocking complex interplay between economic growth, trade openness, financial development, environmental degradation, and environmental sustainability in Bangladesh and Pakistan - Ayesha Khan; Muhammad Zia ur Rehman; Sajjad Ahmad Baig; Muhammad Usman (Environment, Development and Sustainability, 2025)

Green chemistry for prostate health: exploring nature’s toolbox against cancer, inflammation, and hyperplasia - Muavia Sarwar; Hafiz Muhammad Irfan; Alamgeer; Zeeshan Jabbar; Mulazim Hussain Asim; Muhammad Sajjad Hassan; Shoaib Nawaz (Molecular Diversity, 2025)

Microplastic contamination in agricultural soils from mulch films and organic amendments: Transformation mechanism, soil-Biota toxicity, and future perspectives - Bisma Sattar; Guijian Liu; Balal Yousaf; Muhammad Arif; Muhammad Zeeshan Gulzar; Muhammad Irtaza Sajjad Haider; Rabia Safeer; Samra Ijaz; Muhammad Awais Haider; Kiran Aziz (Waste Management, 2025)

Unlocking paleolatitudinal secrets of the early Cretaceous by rare earth element imprints: Implications for seawater chemistry, depositional environments, and paleoclimate in the Talhar Shale, Lower Indus Basin, Pakistan - Rizwan Sarwar Awan; Bo Liu; Hongxia Li; Sajjad Ali; Muhammad Amar Gul; Lingsheng Zhao; Ashar Khan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Flower-like nanoscale Ni(OH)2/MnCO3 electrocatalyst for efficient hydrogen evolution reaction in wide pH range - Zobia Siddique; Salman Noshear Arshad; Muhammad Ali Ehsan; Faryal Aftab; Akhtar Munir; Suryyia Manzoor; Sadia Fatima; Farah Sajjad; Javed Ahmad; Hatice Duran; Senem Çitoğlu (Fuel, 2025)

Assessing Human-Wildlife Conflict in Lakki Marwat, Pakistan: Economic Impacts and People’s Perceptions - Tanveer Khan; Shakeel Ahmad; Tahir Mehmood; Sajjad Rais Khan; Daulat Ullah Khan; Salman Khan; Muhammad Ullah; Ejaz Rahim (European Journal of Wildlife Research, 2025)

Interactive impacts of heat stress and microplastics contamination on the growth and biochemical response of wheat (Triticum aestivum) and maize (Zea mays) plants - Muhammad Sajjad; Saraj Bahadur; Muhammad Aamir Farooq; Ming-Xun Ren (Ecotoxicology, 2025)

Analyzing temporal changes in urban land use and climate dynamics through Google Earth Engine - Muhammad Zaib Arshad; Sajjad Hussain; Zafar Iqbal; Saeed Ahmad Qaisrani; Muhammad Mubeen; Muhammad Tahir; Shankar Karuppannan (Journal of Earth System Science, 2025)

New insights on the potentiality of deep learning techniques in supporting the assessment of some biotic diseases on maize - Sajjad Hussain Qureshi; Sohail Raza Chohan; Muhammad Usman; Muhammad Luqman; Mueen Alam Khan; Baber Ali; Reem M. Aljowaie; Mohamed S. Elshikh; Rashid Iqbal (Journal of Plant Pathology, 2025)

Eco-friendly removal of direct orange 26 dye using lignin-ZnO composite: Optimization and application - Amina Sajjad; Kiran Aftab; Zumaira Siddique; Mohammad Rizwan Khan; Moonis Ali Khan; Abida Kausar; Naushad Ahmad; Muhammad Ali Baig; Rizwan Wahab (Journal of Environmental Management, 2025)

Urban energy efficiency in China: Examining the role of renewable energy, smart Grids, and sustainable design through spatial and policy perspectives (1990–2022) - Muhammad Khalid Anser; Faiza Sajjad; Abdelmohsen A. Nassani; Khalid M. Al-Aiban; Khalid Zaman; Mohamed Haffar (Energy and Buildings, 2025)

A remote sensing and GIS-based analysis of forest cover changes and carbon sequestration trends over three decades - Ali Raza; Neyha Rubab Syed; Romana Fahmeed; Siham Acharki; Sajjad Hussain; Muhammad Zubair; Dinesh Kumar Vishwakarma; Arpit Gaur; Bhaskar Pratap Singh; Abdelaziz M. Okasha; Ahmed Z. Dewidar; Mohamed A. Mattar (Environmental Development, 2025)

Selective Ion Separation via Capacitive Deionization: Current Practices and Future Directions - Hameer Chand; Mohamed Saad Gaballah; Muhammad Irtaza Sajjad Haider; Yangmin Ren; Hongjie Guo; Shuai Wang; Jiahui Ding; He Yang; Chuanjian Cui; Changyong Zhang (Chemical Engineering Journal, 2025)

Subsurface placement of controlled-release blended fertilizers mitigates ammonia volatilization by promoting nitrogen transformation in rice fields - Sajjad Ahmad; Muhammad Yousaf Nadeem; Shen Gao; Quanxin Li; Yanfeng Ding; Zhenghui Liu; Yu Jiang; Weiwei Li; Ganghua Li (Agriculture, Ecosystems & Environment, 2025)

Molecular modeling to design a multiepitope vaccine against emerging tick-borne Yezo virus and its validation through biophysics techniques - Hassan Ayaz; Muhammad Suleman; Asad Ali Shah; Syed Ainul Abideen; Faisal Ahmad; Muhammad Ali; Sajjad Ahmad; Asia Nawaz; Hanbal Ahmad khan; Inam Hussain; Muhammad Irfan; Yasir Waheed (In Silico Pharmacology, 2025)

Rapid and selective E-waste gold extraction from aqua regia by dual redox active-sites of skeleton modulated poly(organo)phosphazenes - Yasir Abbas; Sajjad Ali; Majid Basharat; Hafiz M. Adeel Sharif; Muhammad Ahsan Iqbal; Mohamed Bououdina; Haoliang Wang; Niaz Ali Khan (Chemical Engineering Journal, 2025)

Assessment of Climate Change Impact on Potato-Potato Cropping System Under Semi-arid Environment and Designing of Adaptation Strategies - Sahrish Naz; Mukhtar Ahmed; Ghulam Abbas; Zartash Fatima; Sajjad Hussain; Pakeeza Iqbal; Abdul Ghani; Muhammad Ali; Tahir Hussain Awan; Noreen Samad; Muhammad Aasim; Sezai Ercisli; et al. (Potato Research, 2025)

Development of a hydrodynamic model of the irrigation canal network by using HEC-RAS: a case study of Layyah Canal Division, Pakistan - Numan Ijaz; Sajjad Haider; Muhammad Muaaz (Modeling Earth Systems and Environment, 2025)

First Insights on Sowing Time and Cultivar Selection of Sweet Corn for Optimal Yield and Shelf Life Under Agro-Climatic Conditions of Multan - Iqra Zakir; Shakeel Ahmad; Muhammad Shahzad Saleem; Sajjad Hussain; Halima Nawaz; Talaat Ahmed; Muhammad Fasih Khalid (International Journal of Plant Production, 2025)

Prevalence of Staphylococcus aureus and Antimicrobial Drug Residues in Chicken Liver its Antibiogram Analysis and Implications on Public Health - Gulzar Ahmad; Malik Muhammad Rizwan; Faryal Azam; Muhammad Ijaz; Ainee Urooj Khan; Shamsher Khan; Muhammad Khan; Hafsa Shah; Noor Muhammad; Zia Ur Rahman; Numan Fazal; Sajjad Ullah; et al. (Indian Journal of Microbiology, 2025)

Exploring the morpho-physiological responses of maize to nickel stress modulated by salicylic acid - Atifa Masood; Sumaira Arooj; Muhammad Shahbaz; Noreen Khalid; Muhammad Sajjad; Muhammad Faisal Maqsood; Sunbal Khalil Chaudhari; Abida Abid; Rafia Zainab; Noor Fatima (Cereal Research Communications, 2025)

Unraveling the influence of doleritic intrusions on diagenetic alterations in the Precambrian Utch Khattak Limestone, Gandghar Range, Pakistan - Muhammad Asim; Mumtaz Muhammad Shah; Sajjad Khan (Carbonates and Evaporites, 2025)

In-vitro, in-vivo and computational experiments for the antidiabetic potential of bioactive compound from Notholirion thomsonianum - Abdulaziz Hassan Alhasaniah; Abdul Sadiq; Ahmed Abdullah Al Awadh; Yahya I. Asiri; Meriem Rezigue; Rehman Zafar; Sajjad Ahmad; Muhammad Saeed Jan; Mater H. Mahnashi (Natural Product Research, 2025)

Organic matter and microplastics nexus: A comprehensive understanding of the synergistic impact on soil health - Samra Ijaz; Guijian Liu; Abdul Rehman; Muhammad Irtaza Sajjad Haider; Rabia Safeer; Bisma Sattar; Muhammad Zeeshan Gulzar; Sofia Nosheen; Balal Yousaf (Science of The Total Environment, 2025)

Hydrothermal integrated chemical treatment of microplastics for efficient degradation: Mechanistic insight and degradation behavior - Muhammad Zeeshan Gulzar; Guijian Liu; Balal Yousaf; Muhammad Imran; Muhammad Arif; Muhammad Nauman; Muhammad Irtaza Sajjad Haider; Bisma Sattar; Rabia Safeer; Samra Ijaz; Ruijia Liu (Journal of Water Process Engineering, 2025)

Synergistic defect engineering and z-scheme heterojunction in ultrasonication assisted CuFe LDH and carbon vacancies modified g-C3N4 composite for electrocatalytic water splitting and photocatalytic dye degradation - Muhammad Usman; Khurram Imran Khan; Samia; Sidra Khalid; Faiq Saeed; Abdul Wahab; Muhammad Sajjad Asghar; Ahmad Althobaiti; Alsharef Mohammad; Haitao Dai (Journal of Water Process Engineering, 2025)

Response surface optimization for biodiesel production from chicken fat via transesterification process over CaO-CeO2 catalyst - Hifza Rouf; Rehana Kousar; Zia Ul Haq; Syed Muhammad Wajahat ul Hasnain; Sajjad Haider; Salahuddin Khan; Sadaf Ul Hassan (Sustainable Chemistry and Pharmacy, 2025)

Hexagonal boron nitride: From fundamentals to applications - Sajjad Ali; Pir Muhammad Ismail; Muhammad Humayun; Mohamed Bououdina (Desalination, 2025)

ENSO teleconnections and predictability of the boreal summer temperature over the Arabian Peninsula in C3S and Saudi-KAU seasonal forecast systems - Mansour Almazroui; M. Salman Khalid; Muhammad Adnan Abid; Irfan Ur Rashid; Shahzad Kamil; Haroon Siddiqui; M. Nazrul Islam; Muhammad Ismail; Muhammad Azhar Ehsan; Enda O'Brien; Mazen Asiri; Rayees Ahmed; et al. (Atmospheric Research, 2025)

Exploring the Mechanisms of Halophilic Bacterium SPSB2 and Mannitol in Mitigating Sodium Chloride and Arsenic Stress in Solanum Lycopersicum - Lubna; Muhammad Aizaz; Shima Ahmed Ali Alrumaidhi; Rawan Ahmed Mohammed Alhinai; Reem Saif Mohammed A. L. Kalbani; Ibrahim Khan; Saqib Bilal; Sajjad Asaf; Ahmed AL-Harrasi (Journal of Crop Health, 2025)

Recent perspectives on biotechnological production, modulation and applications of glycerophosphoryl diester phosphodiesterases - Arshia Nazir; Muhammad Sajjad (Biodegradation, 2025)

Immunological assessment of NSFu1: A novel fusion molecule constructed from structural proteins of SARS-CoV-2 for improving COVID-19 antibody detection - Shaista Arif; Mohsina Akhter; Aqsa Anwar; Sania Javaid; Zara Ashi; Mohsin Shad; Asad Rahman; Huda Abbas; Fouzia Ashraf; M. Waheed Akhtar; Muhammad Sajjad (Archives of Microbiology, 2025)

Differential responses of leguminous tree species to drought stress: implications for agroforestry and restoration in arid and semi-arid climates - Muhammad Madnee; Tanveer Hussain; Muhammad Azeem Sabir; Muhammad Abid; Muneeb Khalid; Hussain Ahmad Makki; Sajjad Ali; Nugraha Akbar Nurrochmat (Agroforestry Systems, 2025)

Remote sensing-based flash flood mapping and damage assessment in Dera Ismail Khan, Khyber Pakhtunkhwa, Pakistan - Asif Sajjad; Muhammad Ahmad; Rana Waqar Aslam; Mehnaz Bibi; Anwaar Tabassum (Environmental Monitoring and Assessment, 2025)

The rise of 4D printing Technology: 2D MXenes for different applications - Iftikhar Hussain; Karanpal Singh; B. Kalidasan; Mubasher Ali; Ke-Juan Meng; Muhammad Kashif Aslam; Sabarison Pandiyarajan; Sajjad Hussain; P. Rosaiah; Saood Ali; Ho-Chiao Chuang; Kaili Zhang (Chemical Engineering Journal, 2025)

Enhanced microwave absorption and improved broadband with synergistic effect of nest like self-assembly of CoFe2O4/Co3O4 heterostructured composites - M. Zeeshan Ashfaq; Aamna Ashfaq; Xingxing Cheng; Hongyu Gong; Adil Saleem; Rashid Iqbal; Muhammad Sajjad; Junbin Lu; M. Mamoor; Muhammad K. Majeed (Chemical Engineering Journal, 2025)

The efficacy of egg albumin nanoparticles adjuvanted Clostridium perfringens type D toxoid vaccine in rabbits - Mehwish Saeed; Saad Zafar; Zarreen Sajjad; Rizwan Aslam; Sultan Ali; Muhammad Shahid Mahmood; Mueed Aayan; Maria Sophy; Saqib Umer; Sajjad Ur Rahman; Muhammad Naveed Anwar (Brazilian Journal of Microbiology, 2025)

Food security in Punjab, Pakistan: rural views on climate disasters and their impacts - Muhammad Usman; Asghar Ali; Sajjad Ahmad Baig; Magdalena Radulescu; Azhar Abbas; Rimsha Akram (Environment, Development and Sustainability, 2025)

Isolation and characterization of ureolytic calcifying bacteria from methane hydrate-bearing marine sediments for bio-cementation application - Sahib Zada; Muhammad Rafiq; Wasim Sajjad; Muhammad Afzal; Zheng Su; Liu Lihua (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

From pollutant to purifier: Leveraging plastic waste-derived activated carbon for sustainable water remediation solutions - Hammad Khan; Muhammad Usama; Mohammad Ilyas Khan; Fazal Wahab; Izhar Ahmad; Ali Hamid; Sajjad Hussain; Arslan Maqbool (Journal of Environmental Management, 2025)

Chemistry, biosynthesis, and theranostics of antioxidant flavonoids and polyphenolics of genus Rhododendron: an overview - Amjad Hussain; Sajjad Azam; Rabia Maqsood; Riaz Anwar; Muhammad Sajid Hamid Akash; Hidayat Hussain; Daijie Wang; Muhammad Imran; Katarzyna Kotwica-Mojzych; Shoaib Khan; Shabbir Hussain; Muhammad Adnan Ayub (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Multi-scale computational modeling to identify novel chemical scaffolds as trehalose-6-phosphate phosphatase inhibitors to combat Burkholderia pseudomallei - Sara Noor; Mohammad Abdullah Aljasir; Maryam Bashir; Kalsoom Khan; Sajjad Ahmad; Syed Ainul Abideen; Saifullah Khan; Farhan Siddique; Hamza Ahmad; Khudija Ghani; Madiha Iqbal; Muhammad Irfan; et al. (In Silico Pharmacology, 2025)

Small unmanned aerial vehicle (UAV)-based detection of seasonal micro-urban heat islands for diverse land uses - Junaid Ahmad; Muhammad Sajjad; Jessica Eisma (International Journal of Remote Sensing, 2025)

Alleviation of cadmium stress and improved growth performance of periwinkle (Catharanthus roseus L.) by foliar application of zinc oxide nanoparticles - Muhammad Ahsan; Emanuele Radicetti; Roberto Mancinelli; Hayssam M. Ali; Adnan Younis; Mateen Sajid; Abdul Manan; Sajjad Ali; Mohammad Valipour; Hira Zulfiqar (South African Journal of Botany, 2025)

Correction: Symmetrical Ligand’s Fabricated Porous Silicon Surface Based Photoluminescence Sensor for Metal Detection and Entrapment - Muhammad Saleem; Abrar Hussain; Salah Uddin Khan; Sajjad Haider; Ki Hwan Lee; Sang Hyun Park (Journal of Fluorescence, 2024)

Correction: Synthesis, Invitro Cytotoxic Activity and Optical Analysis of Substituted Schiff Base Derivatives - Muhammad Saleem; Abrar Hussain; Muhammad Hanif; Hufsa Ahmad; Salah Uddin Khan; Sajjad Haider; Muhammad Rafiq; Rizwan Nasir Paracha; Sang Hyun Park (Journal of Fluorescence, 2024)

Correction: Ratiometric Fluorescence and Chromogenic Probe for Trace Detection of Selected Transition Metals - Muhammad Saleem; Abrar Hussain; Muhammad Rauf; Salah Uddin Khan; Sajjad Haider; Muhammad Hanif; Muhammad Rafiq; Sang Hyun Park (Journal of Fluorescence, 2024)

From stress to resilience: Unraveling the molecular mechanisms of cadmium toxicity, detoxification and tolerance in plants - Iqra Noor; Hamza Sohail; Muhammad Tanveer Akhtar; Jiawen Cui; Zhaogeng Lu; Salma Mostafa; Mirza Hasanuzzaman; Sajjad Hussain; Nan Guo; Biao Jin (Science of The Total Environment, 2024)

Highly competent elimination of diverse toxic heavy metal oxo-anions by novel 2D guanidinium-based ionic covalent organic framework - Jerosha Ifthikar; Eman A. Gendy; Imran Mahmood Khan; Ibrahim Khan; Muhammad Sajjad (Next Research, 2024)

Unveiling the biosorption performance of silk fibroin fiber for Pb(II) and Cr(VI) removal: Machine learning and DFT analysis - Muhammad Usman Farooq; Hammad Khan; Muhammad Arshad; Muhammad Usama; Mohammad Ilyas Khan; Sajjad Hussain; Ali Hamid (Journal of Water Process Engineering, 2024)

Modulations in Physiological and Biochemical attributes of Citrus Limon by selenium nanoparticles (SeNPs) under salinity stress - Hummera Nawaz; Khawaja Shafique Ahmad; Iqra Aslam; Athar Mahmood; Ansar Mehmood; Ameer Khan; Muhammad Jamil; Amina Ameer; Muhammad Faraz Khan; Sajjad Hussain (Biocatalysis and Agricultural Biotechnology, 2024)

Earthworms as Catalysts for Climate-Resilient Agriculture: Enhancing Food Security and Water Management in the Face of Climate Change - Muhammad Danish Toor; Abdul Basit; Benedict Okorie; Dibyajyoti Nath; Muhammad Mughees Ud Din; Pawan Kumar Verma; Saleem Sajjad; Izhar Ullah; Hany N. Yousef; Heba I. Mohamed (Water, Air, & Soil Pollution, 2024)

Adenosine A2AR in viral immune evasion and therapy: unveiling new avenues for treating COVID-19 and AIDS - Muhammad Atif; Abdullah Alsrhani; Farrah Naz; Sajjad Ullah; Abualgasim Elgaili Abdalla; Muhammad Ikram Ullah; Bi Bi Zainab Mazhari; Lienda Bashier Eltayeb; Ismail Hamad; Hasan Ejaz (Molecular Biology Reports, 2024)

An SNP based genotyping assay for genes associated with drought tolerance in bread wheat - Abdul Rauf; Muhammad Ali Sher; Umar Farooq; Awais Rasheed; Muhammad Sajjad; Ruilian Jing; Zulqurnain Khan; KOTB A. Attia; Arif Ahmed Mohammed; Sajid Fiaz; Jing Chen; Shoaib Ur Rehman (Molecular Biology Reports, 2024)

Real-time expression and in silico characterization of pea genes involved in salt and water-deficit stress - Muhammad Farooq; Rafiq Ahmad; Muhammad Shahzad; Saad Ur Rehman; Yasar Sajjad; Amjad Hassan; Mohammad Maroof Shah; Amber Afroz; Sabaz Ali Khan (Molecular Biology Reports, 2024)

Performance evaluation of irrigation outlets with physical model study in Indus basin irrigation system of Pakistan - Ghulam Nabi; Fiaz Hussain; Bilal Sajjad; Muhammad Masood; Dengfeng Liu (Environmental Monitoring and Assessment, 2024)

Sedimentology, diagenesis and sequence stratigraphy of the Early–Middle Eocene Chorgali Formation in the Hazara sub-Basin, Northwest Himalayas, Pakistan - Emad Ullah Khan; Shadab Khan; Syed Muhammad Wasim Sajjad; Maryam Saleem; Muhammad Ilyas; Saif Ullah Khan (Carbonates and Evaporites, 2024)

Assessing the potential landslide risk identification in the northern section of CPEC route Pakistan based on Multi-Temporal InSAR approaches - Meer Muhammad Sajjad; Juanle Wang; Daqing Ge; Rehan Khan; Izhar Ahmed; Khan Zada (Journal of Mountain Science, 2024)

Evaluation of morphological and biochemical variations in peas under two widespread abiotic stresses - Muhammad Farooq; Rafiq Ahmad; Muhammad Shahzad; Khalid Ahmad; Yasar Sajjad; Amjad Hassan; Abdul Nazir; Mohammad Maroof Shah; Bibi Kalsoom; Sabaz Ali Khan (Acta Physiologiae Plantarum, 2024)

Nutritional composition assessment and antimicrobial activity of Catostylus perezi , jellyfish blooms along the coast of Pakistan: an awareness to avoid food neophobia in Pakistan - Muhammad Naveed; Malik Wajid Hussain Chan; Sadar Aslam; Fenghuan Wang; Anas Sajjad; Asad Ullah; Nida Saleem; Muhammad Samee Haider; Victoria Arija (Natural Product Research, 2024)

Enhanced effect of electric field on methane pyrolysis and hydrogen production by Ni-Supported MoS2 Catalyst: A molecular dynamics study - Wenjun Zhou; Yu Zhang; Muhammad Sajjad Ahmad; Boxiong Shen; Sibudjing Kawi (Fuel, 2024)

Decoding comparative taste and nutrition regulation in Chinese cabbage via integrated metabolome and transcriptome analysis - Muhammad Sajjad; Shudan Xue; Meijiang Zhou; Guihua Li; Yingchao Xu; Ling Liu; Jitong Zhu; Qitao Meng; Qingmin Jin; Hu Du; Chunpeng Yao; Yujuan Zhong (Food Research International, 2024)

Integrated assessment of groundwater quality dynamics and Land use/land cover changes in rapidly urbanizing semi-arid region - Arif ullah; Sajjad Hussain; Yicheng Wang; Muhammad Awais; Meer Muhammad Sajjad; Nuaman Ejaz; Umar Javed; Muhammad Waqas; Xiao Zhe; Javed Iqbal (Environmental Research, 2024)

Fe/Ni bimetallic magnetic nano-alloy (INBMNA): An efficient heterogeneous catalyst for photo-Fenton-like degradation of phenol in aqueous environment - Muhammad Yaqoob Soomro; Aamna Balouch; Esra Alveroglu; Rimsha Larik; Komal Shah; Sajjad Ali Chang (Environmental Pollution, 2024)

Detection of Mobile and Immobile Solute Transport and Their Residence Time in Saturated Low and High Permeability Soil Layers - Muhammad Zaheer; Ehsan Ul Haq; Ning Huang; Ahmed Amara Konaté; Ghulam Mujtaba Shah; Raja Umer Sajjad; Saad Ahmed Mashwani (Water, Air, & Soil Pollution, 2024)

Comprehensive insights on treatment modalities with conventional and herbal drugs for the treatment of duodenal ulcers - Huma Hameed; Jahangir Hussain; Ana Cláudia Paiva-Santos; Muhammad Zaman; Ali Hamza; Irsa Sajjad; Faria Asad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Adsorptive removal of cationic dyes from wastewater using a novel sodium alginate-based iron oxide nanocomposite hydrogel: DFT and advanced statistical physics modelling - Muhammad Umar; Muhammad Usman Farooq; Muhammad Arshad; Muhammad Usama; Feryal Akbal; Sajjad Hussain; Hammad Khan (Process Safety and Environmental Protection, 2024)

Assessing the physicochemical properties of surface/groundwater of Sudhnoti district, Azad Jammu and Kashmir: Impacts on lindane degradation by photocatalysis - Taj Ur Rahman; Lubna Saba; Ashraf Ali; Wajiha Liaqat; Sanaullah Khan; Javed Ali Khan; Muhammad Aurang Zeb; Sajjad Hussain; Eman Y. Santali; Changseok Han (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Facile synthesis of inherently nitrogen-doped PAN-derived microporous carbons activated with NaNH2 for selective CO2 adsorption and separation - Ghazanfar Nazir; Adeela Rehman; Muhammad Ikram; Muhammad Aslam; Tian C. Zhang; Awais Khalid; Sikandar Aftab; Sajjad Hussain; Hanadi A. Almukhlifi; Amal A. Abdel Hafez; Kwang Heo (Chemical Engineering Journal, 2024)

Comparative growth, biochemical and antioxidative response of Glycine max and Sesamum indicum to MnS nanoparticles - Jehangir Khan; Anila Sajjad; Mah Rukh; Khalid Khan; Syed Waqas Hassan; Muhammad Zia (Biocatalysis and Agricultural Biotechnology, 2024)

Synergistic interactions and reaction mechanisms of biochar surface functionalities in antibiotics removal from industrial wastewater - Muhammad Irtaza Sajjad Haider; Guijian Liu; Balal Yousaf; Muhammad Arif; Kiran Aziz; Aniqa Ashraf; Rabia Safeer; Samra Ijaz; Krzysztof Pikon (Environmental Pollution, 2024)

Sedimentology and reservoir characterization of Upper Cretaceous Kawagarh Formation, Upper Indus Basin, Lesser Himalayas, Pakistan: inferences from petrography, SEM-EDS and petrophysics - Salman Ahmed Khattak; Muhammad Hanif; Sajjad Ahmad; Ihtisham Islam; George Kontakiotis; Evangelia Besiou; Assimina Antonarakou (Carbonates and Evaporites, 2024)

Fluid flow-driven multiphase dolomitization in the Cambrian Jutana Formation, salt range and adjacent area (Pakistan): insights from sedimentological and isotopic analyses - Sajjad Khan; Mumtaz Muhammad Shah (Carbonates and Evaporites, 2024)

Analytical seismic assessment for reinforced concrete moment frame residential buildings constructed in the Soviet Union Era in Almaty, Kazakhstan - Muhammad Sajjad Rashid; Dichuan Zhang; Sung-Woo Moon; Yeraly Shokbarov; Jong Kim (Bulletin of Earthquake Engineering, 2024)

Non-linear ground deformation detection and monitoring using time series InSAR along the coastal urban areas of Pakistan - Sajid Hussain; Bin Pan; Zeeshan Afzal; Wajid Hussain; Yin Jianhui; Meer Muhammad Sajjad; Muhammad Ali (Environmental Science and Pollution Research, 2024)

Development of energy efficient flower-shaped defective TiO2 materials for wastewater remediation of agro-industries and oil refineries - Rab Nawaz; Marlia Mohd Hanafiah; Sajjad Haider; Muzammil Anjum; Mujahid Ali; Rawaiz Khan; Sammia Khurshid; Shafi Ullah; Muhammad Aqif; Adnan Haider; Zaher Abdel Baki (Process Safety and Environmental Protection, 2024)

Multi-criteria decision-making techniques for groundwater potentiality mapping in arid regions: A case study of Wadi Yiba, Kingdom of Saudi Arabia - Nuaman Ejaz; Aftab Haider Khan; Muhammad Waqar Saleem; Amro Mohamed Elfeki; Khalil Ur Rahman; Sajjad Hussain; Safi Ullah; Songhao Shang (Groundwater for Sustainable Development, 2024)

Retraction Note: Impact of credit, liquidity, and systematic risk on financial structure: comparative investigation from sustainable production - Muhammad Sadiq; Sami Alajlani; Muhammed Sajjad Hussain; Rashid Ahmad; Furrukh Bashir; Supat Chupradit (Environmental Science and Pollution Research, 2024)

Retraction Note: The step towards environmental mitigation in Pakistan: do transportation services, urbanization, and financial development matter? - Danish Iqbal Godil; Paiman Ahmad; Muhammad Sajjad Ashraf; Salman Sarwat; Arshian Sharif; Syed Shabib-ul-Hasan; Kittisak Jermsittiparsert (Environmental Science and Pollution Research, 2024)

Assessment of hydrochemical characteristics, health risks and quality of groundwater for drinking and irrigation purposes in a mountainous region of Pakistan - Waqar Azeem Jadoon; Muhammad Zaheer; Abdul Tariq; Raja Umer Sajjad; Memet Varol (Environmental Science and Pollution Research, 2024)
Renowned for its agriculture, livestock, and mining, Zhob district, Pakistan, faces the urgent problem of declining groundwater quality due to natural and human-induced factors. This deterioration poses significant challenges for residents who rely on groundwater for drinking, domestic, and irrigation purposes. Therefore, this novel study aimed to carry out a comprehensive assessment of groundwater quality in Zhob district, considering various aspects such as hydrochemical characteristics, human health risks, and suitability for drinking and irrigation purposes. While previous studies may have focused on one or a few of these aspects, this study integrates multiple analyses to provide a holistic understanding of the groundwater quality situation in the region. Additionally, the study applies a range of common hydrochemical analysis methods (acid–base titration, flame atomic absorption spectrometry, and ion chromatography), drinking water quality index (WQI), irrigation indices, and health risk assessment models, using 19 water quality parameters. This multi-method approach enhances the robustness and accuracy of the assessment, providing valuable insights for decision-makers and stakeholders. The results revealed that means of the majority of water quality parameters, such as pH (7.64), electrical conductivity (830.13 μScm –1 ), total dissolved solids (562.83 mgL –1 ), as well as various anions, and cations, were in line with drinking water norms. However, the water quality index (WQI) predominantly indicated poor drinking water quality (range = 51–75) at 50% sites, followed by good quality (range = 26–50) at 37% of the sites, with 10% of the sites exhibiting very poor quality (range = 76–100). For irrigation purposes, indices such as sodium percent (mean = 31.37%), sodium adsorption ratio (mean = 0.98 meqL –1 ), residual sodium carbonate (– 3.15 meqL –1 ), Kelley’s index (mean = 0.49), and permeability (mean = 49.11%) indicated suitability without immediate treatment. However, the magnesium hazard (mean = 46.11%) and potential salinity (mean = 3.93) demonstrated that prolonged application of groundwater for irrigation needs soil management to avoid soil compaction and salinity. Water samples exhibit characteristics of medium salinity and low alkalinity (C2S1) as well as high salinity and low alkalinity (C3S1) categories. The Gibbs diagram results revealed that rock weathering, including silicate weathering and cation exchange, is the primary factor governing the hydrochemistry of groundwater. The hydrochemical composition is dominated by mixed Ca–Mg–Cl, followed by Na–Cl and Mg–Cl types. Furthermore, the human health risk assessment highlighted that fluoride (F – ) posed a higher risk compared with nitrate (NO 3 – ). Additionally, ingestion was found to pose a higher risk to health compared to dermal contact, with children being particularly vulnerable. The average hazard index (HI) for children was 1.24, surpassing the allowable limit of 1, indicating detrimental health effects on this subpopulation. Conversely, average HI values for adult females (0.59) and adult males (0.44) were within safe levels, suggesting minimal concerns for these demographic groups. Overall, the study’s interdisciplinary approach and depth of analysis make a significant contribution to understanding groundwater quality dynamics and associated risks in Zhob district, potentially informing future management and mitigation strategies.

Synthesis, Invitro Cytotoxic Activity and Optical Analysis of Substituted Schiff Base Derivatives - Muhammad Saleem; Abrar Hussain; Muhammad Hanif; Hufsa Ahmad; Salah Uddin Khan; Sajjad Haider; Muhammad Rafiq; Rizwan Nasir Paracha; Sang Hyun Park (Journal of Fluorescence, 2024)

Integrated AI-driven optimization of Fenton process for the treatment of antibiotic sulfamethoxazole: Insights into mechanistic approach - Saima Gul; Sajjad Hussain; Hammad Khan; Muhammad Arshad; Javaid Rabbani Khan; Artur de Jesus Motheo (Chemosphere, 2024)

RETRACTED: Almond shell-derived biochar decreased toxic metals bioavailability and uptake by tomato and enhanced the antioxidant system and microbial community - Muhammad Imran Ghani; Mohammad Abass Ahanger; Tanveer Ali Sial; Sajjad Haider; Junaid Ali Siddique; Ruidong Fan; Yanjiang Liu; Esmat F. Ali; Manish Kumar; Xing Yang; Jörg Rinklebe; Xiaoyulong Chen; et al. (Science of The Total Environment, 2024)

Activation of persulfate, peroxymonosulfate, and peroxydisulfate using metal-organic framework catalysts for degradation of antibiotics: Identification, quantification, interconversion, and transformation of reactive species - Irfan Ijaz; Aysha Bukhari; Attia Shaheen; Ammara Nazir; Ezaz Gilani; Hina Zain; Shabbir Muhammad; Sajjad Hussain (Journal of Environmental Chemical Engineering, 2024)

Insights into the biogeochemical transformation, environmental impacts and biochar-based soil decontamination of antimony - Rabia Safeer; Guijian Liu; Balal Yousaf; Aniqa Ashraf; Muhammad Irtaza Sajjad Haider; Ayesha Imtiyaz Cheema; Samra Ijaz; Audil Rashid; Anila Sikandar; Krzysztof Pikoń (Environmental Research, 2024)

Evaluating the relative influence of climate and human activities on recent vegetation dynamics in West Bengal, India - Abhishek Banerjee; Shichang Kang; Michael E. Meadows; Wasim Sajjad; Ali Bahadur; Muhammad Farhan Ul Moazzam; Zilong Xia; Joseph Mango; Bappa Das; Kelly L. Kirsten (Environmental Research, 2024)

Application of SUMO fusion technology for the enhancement of stability and activity of lysophospholipase from Pyrococcus abyssi - Arshia Nazir; Mohsin Shad; Hafiz Muzzammel Rehman; Naseema Azim; Muhammad Sajjad (World Journal of Microbiology and Biotechnology, 2024)

Morpho-Physiological and Enzymatic Responses of Zinnia (Zinnia elegans L.) to Different Metal Hoarded Wastewaters - Muhammad Ahsan; Adnan Younis; Muhammad Raheel; Imran Khalid; Hafiz Tassawar Abbas; Waqas Ashraf; Adil Mihoub; Emanuele Radicetti; Muhammad Farhan Saeed; Sajjad Ali; Mohammad Valipour; Aftab Jamal (Journal of Soil Science and Plant Nutrition, 2024)

Integrated sedimentary and diagenetic constraints for delineating the reservoir potential of Jurassic carbonate sequences in the autochthonous Samana Suk Formation, Attock-Cherat Nizampur Area, Pakistan - Muhammad Ibrar; Sajjad Khan; Mehboob Ur Rashid; George Kontakiotis; Ihtisham Islam; Hammad Tariq Janjuhah; Assimina Antonarakou (Carbonates and Evaporites, 2024)

Digital technology integration in business model innovation for carbon neutrality: An evolutionary process model for SMEs - Leven J. Zheng; Justin Zuopeng Zhang; Louisa Yee Sum Lee; Sajjad M. Jasimuddin; Muhammad Mustafa Kamal (Journal of Environmental Management, 2024)

Temperature-dependent transformation of microbial community: A systematic approach to analyzing functional microbes and biogas production - Ali Bahadur; Lu Zhang; Wei Guo; Wasim Sajjad; Nikhat Ilahi; Abhishek Banerjee; Shah Faisal; Muhammad Usman; Tuo Chen; Wei Zhang (Environmental Research, 2024)

Symmetrical Ligand’s Fabricated Porous Silicon Surface Based Photoluminescence Sensor for Metal Detection and Entrapment - Muhammad Saleem; Abrar Hussain; Salah Uddin Khan; Sajjad Haider; Ki Hwan Lee; Sang Hyun Park (Journal of Fluorescence, 2024)

The development of plastic waste and sewage sludge co-pyrolyzed biochar composites with improved interfacial characteristics for the effective removal of ciprofloxacin - Aniqa Ashraf; Guijian Liu; Muhammad Arif; Balal Yousaf; Pervaiz Akhtar; Audil Rashid; Humaira Gulzaman; Rabia Safeer; Muhammad Saqib Rashid; Muhammad Irtaza Sajjad Haider (Process Safety and Environmental Protection, 2024)

Bacteria populating freshly appeared supraglacial lake possess metals and antibiotic-resistant genes - Wasim Sajjad; Nikhat Ilahi; Abdul Haq; Zhanhuan Shang; Ghulam Nabi; Muhammad Rafiq; Ali Bahadur; Abhishek Banerjee; Shichang Kang (Environmental Research, 2024)

Integrating DFT and machine learning for the design and optimization of sodium alginate-based hydrogel adsorbents: Efficient removal of pollutants from wastewater - Muhammad Umar; Hammad Khan; Sajjad Hussain; Muhammad Arshad; Hyeok Choi; Eder C. Lima (Environmental Research, 2024)

Cryosphere: a frozen home of microbes and a potential source for drug discovery - Sahib Zada; Mohsin Khan; Zheng Su; Wasim Sajjad; Muhammad Rafiq (Archives of Microbiology, 2024)

Exploring the underlying correlation between microbiota, immune system, hormones, and inflammation with breast cancer and the role of probiotics, prebiotics and postbiotics - Muhammad Summer; Ayesha Sajjad; Shaukat Ali; Tauqeer Hussain (Archives of Microbiology, 2024)

Retraction Note: evaluating the environmental impact and economic practicability of solar home lighting systems: a roadmap towards clean energy for ecological sustainability - Shahid Ali; Qingyou Yan; Muhammad Irfan; Muhammad Sajjad Hussain; Muhammad Arshad (Environmental Science and Pollution Research, 2024)

Ratiometric Fluorescence and Chromogenic Probe for Trace Detection of Selected Transition Metals - Muhammad Saleem; Abrar Hussain; Muhammad Rauf; Salah Uddin Khan; Sajjad Haider; Muhammad Hanif; Muhammad Rafiq; Sang Hyun Park (Journal of Fluorescence, 2024)

Temperature drives microbial communities in anaerobic digestion during biogas production from food waste - Tuo Chen; Lu Zhang; Wei Guo; Wei Zhang; Wasim Sajjad; Nikhat Ilahi; Muhammad Usman; Shah Faisal; Ali Bahadur (Environmental Science and Pollution Research, 2024)

Urbanization-led land cover change impacts terrestrial carbon storage capacity: A high-resolution remote sensing-based nation-wide assessment in Pakistan (1990–2020) - Mirza Waleed; Muhammad Sajjad; Muhammad Shareef Shazil (Environmental Impact Assessment Review, 2024)

Iron Oxide-Chitosan-Based Nanocomposite for Efficient Fluoride Removal From Drinking Water - Suraya Samejo; Jameel Ahmed Baig; Tasneem Gul Kazi; Hassan Imran Afridi; Saima Perveen; Muhammad Umer Frooq; Khalil Akhtar; Shakoor Ahmed Solangi; Fahad Abbasi; Sajjad Hussain (Water, Air, & Soil Pollution, 2024)

Comparative evaluation of techniques for missing rainfall data estimation in arid regions: case study of Al-Madinah Al-Munawarah, Saudi Arabia - Burhan Niyazi; Sajjad Hussain; Amro M. Elfeki; Milad Masoud; Muhammad Awais (Theoretical and Applied Climatology, 2024)

Disaster mapping and assessment of Pakistan’s 2022 mega-flood based on multi-source data-driven approach - Juanle Wang; Kai Li; Lina Hao; Chen Xu; Jingxuan Liu; Zheng Qu; Xinrong Yan; Meer Muhammad Sajjad; Yamin Sun (Natural Hazards, 2024)

Male sterility systems and their applications in hybrid wheat breeding - Ayesha Farooq; Uzair Muhammad Khan; Muhammad Ahsan Khan; Zulfqar Ali; Rizwana Maqbool; Muhammad Sajjad (Cereal Research Communications, 2024)

Silicon-nanoparticles loaded biochar for soil arsenic immobilization and alleviation of phytotoxicity in barley: Implications for human health risk - Muhammad Asif Naeem; Abrar Shabbir; Muhammad Imran; Sajjad Ahmad; Muhammad Shahid; Behzad Murtaza; Muhammad Amjad; Waqas-ud-Din Khan (Environmental Science and Pollution Research, 2024)

Epigenetic insight into floral transition and seed development in plants - Tahir Mahmood; Shoupu He; Muhammad Abdullah; Muhammad Sajjad; Yinhua Jia; Sunny Ahmar; Guoyong Fu; Baojun Chen; Xiongming Du (Plant Science, 2024)

Hydrothermal synthesis of ZnO@MoTe2 nanocomposite as excellent electrocatalyst for hydrogen evolution reaction (HER) - Saeed D. Alahmari; Salma Aman; Soumaya Gouadria; Sajjad Ahmad Khan; Abdullah G. Al-Sehemi; A.M.A. Henaish; Naseeb Ahmad; Zubair Ahmad; Taha Abdel Mohaymen Taha; Hafiz Muhammad Tahir Farid (Fuel, 2024)

Investigation of the evolved pyrolytic products and energy potential of Bagasse: experimental, kinetic, thermodynamic and boosted regression trees analysis - Yu Zhang; Muhammad Raashid; Xiaoqian Shen; Muhammad Waqas Iqbal; Imtiaz Ali; Muhammad Sajjad Ahmad; David S.A. Simakov; Ali Elkamel; Boxiong Shen (Bioresource Technology, 2024)

Meta-review on Perforation Model of Subarachnoid Hemorrhage in Mice: Filament Material as a Possible Moderator of Mortality - Serdar Alpdogan; Timo Sander; Rui Zhang; Dilaware Khan; Xuanchen Li; Huakang Zhou; Ke Li; Ann-Christin Nickel; Baolong Zheng; Anastasiya Skryabin; Simon Schieferdecker; Björn B. Hofmann; et al. (Translational Stroke Research, 2024)
Robust preclinical models are inevitable for researchers to unravel pathomechanisms of subarachnoidal hemorrhage (SAH). For the mouse perforation model of SAH, the goal of this meta-review was the determination of variances in mortality, SAH severity grade, and vasospasm, and their experimental moderators, as many researchers are facing with incomparable results. We searched on the databases PubMed , Embase , and Web of Science for articles describing in vivo experiments using the SAH perforation mouse model and measuring mortality, SAH grade, and/or vasospasm. After screening, 42 articles (total of 1964 mice) were included into systematic review and meta-analysis. Certain model characteristics were insufficiently reported, e.g., perforation location (not reported in six articles), filament (material ( n = 15) and tip texture ( n = 25)), mouse age ( n = 14), and weight ( n = 10). Used injective anesthetics and location of perforation showed large variation. In a random-effects meta-analysis, the overall animal mortality following SAH was 21.3% [95% CI: 17.5%, 25.7%] and increased with longer observational periods. Filament material significantly correlated with animal mortality ( p = 0.024) after exclusion of hyperacute studies (time after SAH induction < 24 h). Reported mean SAH grade was 10.7 [9.6, 11.7] on the scale of Sugawara (J Neurosci Methods 167:327–34, 2008). Furthermore, mean diameter of large cerebral arteries after SAH was reduced by 27.6% compared to sham-operated non-SAH mice. Uniforming standards of experimental procedures and their reporting are indispensable to increase overall comparability.

Retraction Note: Ameliorative effect of two structurally divergent hydrazide derivatives against DSS-induced colitis by targeting Nrf2 and NF-κB signaling in mice - Ashrafullah Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Sajjad Ahmad; Muhammad Usman Amin; Muhammad Naeem Ahmed; Zia‑ur‑Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Assessment of future prediction of urban growth and climate change in district Multan, Pakistan using CA-Markov method - Sajjad Hussain; Muhammad Mubeen; Wajid Nasim; Faisal Mumtaz; Hazem Ghassan Abdo; Raoof Mostafazadeh; Shah Fahad (Urban Climate, 2024)

Microbial diversity and community structure dynamics in acid mine drainage: Acidic fire with dissolved heavy metals - Wasim Sajjad; Nikhat Ilahi; Shichang Kang; Ali Bahadur; Abhishek Banerjee; Sahib Zada; Barkat Ali; Muhammad Rafiq; Guodong Zheng (Science of The Total Environment, 2024)

Magnetic solid phase extraction of aminoglycosides residue in chicken egg samples using Fe3O4-GO-Agarose-Chitosan composite - Muhammad Sajjad; Rasmiah Almufarij; Zeeshan Ali; Muhammad Sajid; Nadeem Raza; Suryyia Manzoor; Muhammad Hayat; Ehab A. Abdelrahman (Food Chemistry, 2024)

Patterns of bacterial communities in the rhizosphere and rhizoplane of alpine wet meadows - Awais Iqbal; Muhammad Maqsood Ur Rehman; Wasim Sajjad; Abraham Allan Degen; Muhammad Rafiq; Niu Jiahuan; Salman Khan; Zhanhuan Shang (Environmental Research, 2024)

Nanoscale enhancements in perovskite-based photovoltaics - Sikandar Aftab; Xin Li; Sajjad Hussain; Muhammad Aslam; Altaf Hussain Rajpar; Abdullah G. Al-Sehemi (Chemical Engineering Journal, 2024)

2D Ti3C2Tx-MXene nanosheets and graphene oxide based highly sensitive humidity sensor for wearable and flexible electronics - Waqas Waheed; Shoaib Anwer; Muhammad Umair Khan; Muhammad Sajjad; Anas Alazzam (Chemical Engineering Journal, 2024)

Radon concentration in spring water as an indicator of seismic activity: a case study of the Muzaffarabad Fault in Pakistan - Sayed Qamar Abbas; Jahanzeb Khan; Muhammad Tayyib Riaz; Muhammad Rafique; Ali Zaman; Sajjad Khan (Environmental Monitoring and Assessment, 2024)

Genome-wide identification and characterization of wall-associated kinases, molecular docking and polysaccharide elicitation of monoterpenoid indole alkaloids in micro-propagated Catharanthus roseus - Jawad Ahmed; Yasar Sajjad; Aasia Latif; Mohammad Saeed Lodhi; Muhammad Huzafa; Chen Situ; Raza Ahmad; Muhammad Maroof Shah; Amjad Hassan (Journal of Plant Research, 2024)

Characterization of water-deficit tolerance in Upland cotton (Gossypium hirsutum L.) assessing morphological, biochemical, molecular and yield attributes - Muhammad Saeed; Muhammad Naeem; Alia Javed; Shagufta Perveen; Iqra Sajjad; Muhammad Zaid Yousaf; M. Shahid Munir Chohan; Muhammad Riaz; Sana Ullah; Xianliang Song (Acta Physiologiae Plantarum, 2024)

Design and Exploration of Benzene Like Azobis Triazoles for Long-range Push-Pull Photo-Switching Attributes - Abrar U. Hassan; Sajjad H. Sumrra; Muhammad Zubair; Ayesha Mohyuddin; Ghulam Mustafa (Journal of Fluorescence, 2023)

Unleashing the dye adsorption potential of polyaminoimide homopolymer: DFT, statistical physics, site energy and pore size distribution analyses - Nabeel Hussain; Hammad Khan; Sajjad Hussain; Muhammad Arshad; Muhammad Umar; Fazal Wahab (Journal of Environmental Chemical Engineering, 2023)

Corrigendum to “Automated anomalous behaviour detection in soil radon gas prior to earthquakes using computational intelligence techniques” [J. Environ. Radioact. 203 (2019) 48-54] - Aleem Dad Khan Tareen; Asim Khawaja; Kimberlee Jane Kearfott; Muhammad Rafique; Malik Sajjad Ahmed Nadeem; Talat Iqbal; Saeed Ur Rahman (Journal of Environmental Radioactivity, 2023)

High prevalence of antibiotic-resistant and metal-tolerant cultivable bacteria in remote glacier environment - Wasim Sajjad; Barkat Ali; Hewen Niu; Nikhat Ilahi; Muhammad Rafiq; Ali Bahadur; Abhishek Banerjee; Shichang Kang (Environmental Research, 2023)

Sustainable wastewater purification with crab shell-derived biochar: Advanced machine learning modeling & experimental analysis - Amina Bibi; Hammad Khan; Sajjad Hussain; Muhammad Arshad; Fazal Wahab; Muhammad Usama; Khurram Khan; Feryal Akbal (Bioresource Technology, 2023)

Controlled-release potassium blended fertilizer mitigates greenhouse gas emissions in paddy fields - Sajjad Ahmad; Shen Gao; Quanxin Li; Muhammad Yousaf Nadeem; Weike Tao; Fei Yang; Yanfeng Ding; Zhenghui Liu; Ganghua Li (Nutrient Cycling in Agroecosystems, 2023)

Correction to: Flavonoids: a review on biosynthesis and transportation mechanism in plants - Muhammad Aamir Manzoor; Irfan Ali Sabir; Iftikhar Hussain Shah; Muhammad Waheed Riaz; Shamsur Rehman; Cheng Song; Gouhui Li; M. Sanaullah Malik; Ghulam Abbas Ashraf; Muhammad Sajjad Haider; Yunpeng Cao; Muhammad Abdullah (Functional & Integrative Genomics, 2023)

Comparison of As removal efficiency and health risks from aqueous solution using as-synthesized Fe0 and Cu0: modelling, kinetics and reusability - Behzad Murtaza; Asad Ali; Muhammad Imran; Abdullah A. Al-Kahtani; Zeid A. ALOthman; Natasha Natasha; Muhammad Shahid; Noor S. Shah; Muhammad Asif Naeem; Sajjad Ahmad; Ghulam Murtaza (Environmental Geochemistry and Health, 2023)

Geochemical Characterization of Organic Rich Black Rocks of the Niutitang Formation to Reconstruct the Paleoenvironmental Settings during Early Cambrian Period from Xiangxi Area, Western Hunan, China - Rizwan Sarwar Awan; Chenglin Liu; Ashar Khan; Khawaja Hasnain Iltaf; Qibiao Zang; Yuping Wu; Sajjad Ali; Muhammad Amar Gul (Journal of Earth Science, 2023)

Unlocking the secrets of soil microbes: How decades-long contamination and heavy metals accumulation from sewage water and industrial effluents shape soil biological health - Idrees Haider; Muhammad Arif Ali; Muhammad Sanaullah; Niaz Ahmed; Sajjad Hussain; Muhammad Taimoor Shakeel; Syed Atif Hasan Naqvi; Javeed Shabbir Dar; Mahmoud Moustafa; Mohammed O. Alshaharni (Chemosphere, 2023)

Exploring the electrochemical properties of CuSe-decorated NiSe2 nanocubes for battery-supercapacitor hybrid devices - Mudassir Hayat; Yuxue Zhou; Muhammad Zia Ullah Shah; Muhammad Sana ullah; Muhammad Bilal Hanif; Hongying Hou; Umar Arif; Shaukat Khan; Ahmed M. Hassan; Ammar M. Tighezza; Muhammad Sajjad; Raghavender Vadla (Chemosphere, 2023)

Size-resolved ambient bioaerosols concentration, antibiotic resistance, and community composition during autumn and winter seasons in Qatar - Bilal Sajjad; Kashif Rasool; Azhar Siddique; Khadeeja Abdul Jabbar; Shimaa S. El-Malaha; Muhammad Umar Sohail; Fares Almomani; M. Rami Alfarra (Environmental Pollution, 2023)

Proline coated ZnO NPs as nanofertilizer against drought stress: an in vitro study to Coriandrum sativum - Saad Hanif; Anila Sajjad; Muhammad Zia (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Synergistic effect of glycine betain-ZnO nanocomposite in vitro for the amelioration of drought stress in coriander - Saad Hanif; Anila Sajjad; Muhammad Zia (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

An efficient virus-induced gene silencing of PDS gene in Solanum lycopersicum (cv. Rio Grande) and its functional analysis - Iqra Mehboob; Muhammad Mughees; Ayesha Baig; Shaukat Ali; Yasar Sajjad; Shahid Iqbal; Zahoor Hussain; Sajid Fiaz; Farhat Abbas; Kotb A. Attia; Asmaa M. Abushady; Mohammad Maroof Shah (Brazilian Journal of Botany, 2023)

Multiple design and modelling approaches for the optimisation of carbon felt electro-Fenton treatment of dye laden wastewater - Hammad Khan; Sajjad Hussain; Muhammad Amad Ud Din; Muhammad Arshad; Fazal Wahab; Usman Hassan; Abad Khan (Chemosphere, 2023)

Experimental assessment of retrofitted damaged mortarless dry stacked interlocking masonry walls - Saeed Akbar; Akhtar Gul; Inayat Ullah Khan; Muhammad Haseeb; Khan Shahzada; Sajjad Wali Khan; Naveed Ahmad (Soil Dynamics and Earthquake Engineering, 2023)

Tailoring triple charge (O2−/H+/e−) conducting nature of Fe-based lanthanum doped samarium oxides for ceramic fuel cells (CFCs) - Muhammad Yousaf; Yuzheng Lu; Majid Niaz Akhtar; Ali Sarosh Khawaja; Khalid Mujasam Batoo; Sajjad Hussain; Asma Noor; Muhammad Akbar; Hu Enyi; M.A.K Yousaf Shah; Naveed Mushtaq; Bin Zhu (Fuel, 2023)

Simultaneous removal of Norfloxacin, Ciprofloxacin, and copper from aqueous solution by chitosan and MXene functionalized graphene oxide ternary composite based on anion-synergistic interaction - Aysha Bukhari; Irfan Ijaz; Ezaz Gilani; Ammara Nazir; Hina Zain; Shabbir Muhammad; Awais Bukhari; Attia shaheen; Sajjad Hussain (Chemical Engineering Journal, 2023)

Assessing total erythrocyte count as a potential attribute for estimating hemoglobin in Cholistani cattle - Umer Farooq; Musadiq Idris; Nouman Sajjad; Muhammad Abrar Afzal (Tropical Animal Health and Production, 2023)

Modelling Electricity Consumption During the COVID19 Pandemic: Datasets, Models, Results and a Research Agenda - Zulfiqar Ahmad Khan; Tanveer Hussain; Amin Ullah; Waseem Ullah; Javier Del Ser; Khan Muhammad; Muhammad Sajjad; Sung Wook Baik (Energy and Buildings, 2023)

Copper oxide nanoparticles: In vitro and in vivo toxicity, mechanisms of action and factors influencing their toxicology - Humna Sajjad; Anila Sajjad; Rida Tul Haya; Muhammad Mustajab Khan; Muhammad Zia (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Photocatalytic and Antibacterial Potential of Chitosan Supported Nickel Oxide/Zinc Oxide Composite Synthesized by Alcohothermal Method - Amna Yasin; Tousif Hussain; Riaz Ahmad; Urooj Shuaib; Muhammad Amjad; Sajjad Ahmad; M. Imranullah (Water, Air, & Soil Pollution, 2023)

Flavonoids: a review on biosynthesis and transportation mechanism in plants - Muhammad Aamir Manzoor; Irfan Ali Sabir; Iftikhar Hussain Shah; Muhammad Waheed Riaz; Shamsur Rehman; Cheng Song; Gouhui Li; M. Sanaullah Malik; Ghulam Abbas Ashraf; Muhammad Sajjad Haider; Yunpeng Cao; Muhammad Abdullah (Functional & Integrative Genomics, 2023)

Fabrication and Evaluation of Anticancer Potential of Eugenol Incorporated Chitosan-Silver Nanocomposites: In Vitro, In Vivo, and In Silico Studies - Hamid Saeed Shah; Sumera Zaib; Muhammad Sarfraz; A. Alhadhrami; Mohamed M. Ibrahim; Aamir Mushtaq; Faisal Usman; Memoona Ishtiaq; Muhammad Sajjad; Hafiz Muhammad Mazhar Asjad; Umar Farooq Gohar (AAPS PharmSciTech, 2023)

New developments in gas sensing using various two-dimensional architectural designs - Sikandar Aftab; Muhammad Zahir Iqbal; Sajjad Hussain; Hosameldin Helmy Hegazy; Fahmid Kabir; Syed Hassan Abbas Jaffery; Ganesh Koyyada (Chemical Engineering Journal, 2023)

Lupeol, a plant triterpenoid mitigates salt induced stress: growth and antioxidative response of Brassica nigra under in vitro condition - Muhammad Zia; Joham Sarfraz Ali; Saad Hanif; Anila Sajjad; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Pathway analysis of food security by employing climate change, water, and agriculture nexus in Pakistan: partial least square structural equation modeling - Muhammad Usman; Asghar Ali; Muhammad Khalid Bashir; Khalid Mushtaq; Abdul Ghafoor; Fiza Amjad; Muhammad Hashim; Sajjad Ahmad Baig (Environmental Science and Pollution Research, 2023)

Has Pakistan learned from disasters over the decades? Dynamic resilience insights based on catastrophe progression and geo-information models - Muhammad Sajjad; Zulfiqar Ali; Mirza Waleed (Natural Hazards, 2023)

Occurrence and risk evaluation of endocrine-disrupting chemicals in wastewater and surface water of Lahore, Pakistan - Muhammad Ashfaq; Yan Li; Muhammad Zubair; Muhammad Saif Ur Rehman; Sajjad Hussain Sumrra; Muhammad Faizan Nazar; Ghulam Mustafa; Muhammad Tahir Fazal; Humayun Ashraf; Qian Sun (Environmental Geochemistry and Health, 2023)

Do farmers’ risk perception, adaptation strategies, and their determinants benefit towards climate change? Implications for agriculture sector of Punjab, Pakistan - Muhammad Usman; Asghar Ali; Muhammad Khalid Bashir; Magdalena Radulescu; Khalid Mushtaq; Abdulazeez Hudu Wudil; Sajjad Ahmad Baig; Rimsha Akram (Environmental Science and Pollution Research, 2023)

Optimized photodegradation of palm oil agroindustry waste effluent using multivalent manganese–modified black titanium dioxide - Rab Nawaz; Sajjad Haider; Muzammil Anjum; Vipin Kumar Oad; Adnan Haider; Rawaiz Khan; Muhammad Aqif; Tahir Hanif; Nasruulah Khan (Environmental Science and Pollution Research, 2023)

Exploration of the bioenergy potential of Dactyloctenium aegyptium through pyrolysis, kinetics, and thermodynamic parameters to produce clean fuels and biochemicals - Hesham Alhumade; Omar S. Alayed; Muhammad Waqas Iqbal; Ayesha Shahid; Tanveer Iqbal; Muhammad Sajjad Ahmad; Ali Elkamel; Yusuf Al-Turki; Muhammad Aamer Mehmood; Ghulam Abbas Ashraf (Fuel, 2023)

TGF-β Activated Kinase 1 (TAK1) Is Activated in Microglia After Experimental Epilepsy and Contributes to Epileptogenesis - Dilaware Khan; Peter Bedner; Julia Müller; Fabienne Lülsberg; Lukas Henning; Marco Prinz; Christian Steinhäuser; Sajjad Muhammad (Molecular Neurobiology, 2023)
Increasing evidence suggests that inflammation promotes epileptogenesis. TAK1 is a central enzyme in the upstream pathway of NF-κB and is known to play a central role in promoting neuroinflammation in neurodegenerative diseases. Here, we investigated the cellular role of TAK1 in experimental epilepsy. C57Bl6 and transgenic mice with inducible and microglia-specific deletion of Tak1 (Cx3cr1 CreER :Tak1 fl/fl ) were subjected to the unilateral intracortical kainate mouse model of temporal lobe epilepsy (TLE). Immunohistochemical staining was performed to quantify different cell populations. The epileptic activity was monitored by continuous telemetric electroencephalogram (EEG) recordings over a period of 4 weeks. The results show that TAK1 was activated predominantly in microglia at an early stage of kainate-induced epileptogenesis. Tak1 deletion in microglia resulted in reduced hippocampal reactive microgliosis and a significant decrease in chronic epileptic activity. Overall, our data suggest that TAK1-dependent microglial activation contributes to the pathogenesis of chronic epilepsy.

An overview of genome engineering in plants, including its scope, technologies, progress and grand challenges - Muhammad Sufyan; Umar Daraz; Sajjad Hyder; Usman Zulfiqar; Rashid Iqbal; Sayed M. Eldin; Farzana Rafiq; Naveed Mahmood; Khurram Shahzad; Muhammad Uzair; Sajid Fiaz; Iftikhar Ali (Functional & Integrative Genomics, 2023)

RETRACTED ARTICLE: Evaluating the environmental impact and economic practicability of solar home lighting systems: a roadmap towards clean energy for ecological sustainability - Shahid Ali; Qingyou Yan; Muhammad Irfan; Muhammad Sajjad Hussain; Muhammad Arshad (Environmental Science and Pollution Research, 2023)

Impact of technology on the relation between disaggregated energy consumption and CO2 emission in populous countries of Asia - Tang Zhengxia; Zakia Batool; Sajjad Ali; Mohammad Haseeb; Vipin Jain; Syed Muhammad Faraz Raza; Prasun Chakrabarti (Environmental Science and Pollution Research, 2023)

Hydrothermal assisted synthesis of hierarchical SnO2 micro flowers with CdO nanoparticles based membrane for energy storage applications - Ehsan Ullah; Muhammad Zia Ullah Shah; Syed Awais Ahmad; Muhammad Sajjad; Shaukat Khan; Fatimah M. Alzahrani; Adel E.M. Yahya; Sayed M. Eldin; Bhargav Akkinepally; A. Shah; Shenghui Guo (Chemosphere, 2023)

Characterizing spatial–temporal drought risk heterogeneities: A hazard, vulnerability and resilience-based modeling - Ali Khoshnazar; Gerald Corzo Perez; Muhammad Sajjad (Journal of Hydrology, 2023)

Optimization of Citric Acid and EDTA Levels Under Ni Stress Using Rapeseed Brassica napus L. for Phytoremediation - Humera Nawaz; Naila Asghar; Aamir Ali; Amina Ameer; Muhammad Asif Shehzad; Fahim Nawaz; Ansar Mehmood; Muhammad Sajjad Iqbal; Ummar Iqbal; Muhammad Kaleem; Ameer Khan; Khawaja Shafique Ahmad (Water, Air, & Soil Pollution, 2023)

Three research priorities for just and sustainable urban systems: Now is the time to refocus - Joe F. Bozeman; Shauhrat S. Chopra; Philip James; Sajjad Muhammad; Hua Cai; Kangkang Tong; Maya Carrasquillo; Harold Rickenbacker; Destenie Nock; Weslynne Ashton; Oliver Heidrich; Sybil Derrible; et al. (Journal of Industrial Ecology, 2023)
Now is the time to refocus efforts in urban research and design. A changing climate and extreme weather events are presenting unique challenges to urban systems around the world. These challenges illuminate the social barriers that accompany disruptive events such as resource inequities and injustices. In this perspective, we provide three research priorities for just and sustainable urban systems that help to address these matters. The three research priorities are: (1) social equity and justice, (2) circularity, and (3) digital twins. Conceptual context and future research directions are provided for each. For social equity and justice, the future directions are mandatory equity analysis and inclusionary practices, understanding and reconciling historical injustices, and intentional integration with diverse community stakeholders. For circularity applications, they are better metrics for integration, more robust evaluation frameworks, and dynamic modeling at multiple spatial and temporal scales. Future directions for digital twins include developing principles to reduce complexity, integrating model and system components, and reducing barriers to data access. These research priorities are core to meeting several of the United Nations Sustainable Development Goals (i.e., 1—No Poverty, 8—Decent Work and Economic Growth, 10—Reduced Inequalities, and 11—Sustainable Cities and Communities). Useful social and technical matters are discussed throughout, where we highlight the importance of prioritizing localized research efforts, provide guidance for community‐engaged research and co‐development practices, and explain how these priorities interact to align with the evolving field of industrial ecology.

A three-dimensional active biochar for sintering in steel industry and remove methylene blue by synergistic activation of H3PO4 and ZnCl2 - Yu Zhang; Boxiong Shen; Muhammad Sajjad Ahmad; Wenjun Zhou; Rana Rehan Khalid; Muhammad Ibrahim; Awais Bokhari (Fuel, 2023)

Modelling wellbeing of farmers by using nexus of climate change risk perception, adaptation strategies, and their drivers on irrigation water in Pakistan - Muhammad Usman; Asghar Ali; Muhammad Khalid Bashir; Sajjad Ahmad Baig; Khalid Mushtaq; Azhar Abbas; Rimsha Akram; Muhammad Shahzad Iqbal (Environmental Science and Pollution Research, 2023)

Unraveling the mutualistic interaction between endophytic Curvularia lunata CSL1 and tomato to mitigate cadmium (Cd) toxicity via transcriptomic insights - Sajjad Asaf; Rahmatullah Jan; Muhammad Aaqil Khan; Lubna; Abdul Latif Khan; Saleem Asif; Saqib Bilal; Waqar Ahmad; Muhammad Waqas; Kyung-Min Kim; Ahmed AL-Harrasi; In-Jung Lee (Science of The Total Environment, 2023)

Abundance, spatial distribution, and characteristics of microplastics in agricultural soils and their relationship with contributing factors - Muhammad Amjad Khan; Qing Huang; Sardar Khan; Qingqing Wang; Jingjing Huang; Shah Fahad; Muhammad Sajjad; Yin Liu; Ondřej Mašek; Xiaohui Li; Junfeng Wang; Xiaomao Song (Journal of Environmental Management, 2023)

Leveraging machine learning and remote sensing to monitor long-term spatial-temporal wetland changes: Towards a national RAMSAR inventory in Pakistan - Ansa Shafi; Shengbo Chen; Mirza Waleed; Muhammad Sajjad (Applied Geography, 2023)

The inclusive analysis of green technology implementation impacts on employees age, job experience, and size in manufacturing firms: empirical assessment - Sajjad Alam; Jianhua Zhang; Muhammad Usman Shehzad; Fredrick Ahenkora Boamah; Bingbing Wang (Environment, Development and Sustainability, 2023)

Ecological health risk assessment of microplastics and heavy metals in sediments, water, hydrophytes (Alternanthera philoxeroides, Typha latifolia, and Ipomoea carnea), and fish (Labeo rohita) in Marala wetlands in Sialkot, Pakistan - Komal Arshad; Muhammad Aqeel; Ali Noman; Atia Nazir; Adeel Mahmood; Zarrin Fatima Rizvi; Wajiha Sarfraz; Sajjad Hyder; Shanza Zaka; Noreen Khalid (Environmental Science and Pollution Research, 2023)

How does dolomite application affect the greenhouse gases emissions from the terrestrial environment? – A global synthesis - Muhammad Umair Hassan; Maria Batool; Taimoor Hassan Farooq; Muhammad Saleem Arif; Muhammad Aamer; Muhammad Ahmed Waqas; Gadah Albasher; Maryium Sajjad; Awais Shakoor (Fuel, 2023)

Efficacy of endophytic SB10 and glycine betaine duo in alleviating phytotoxic impact of combined heat and salinity in Glycine max L. via regulation of redox homeostasis and physiological and molecular responses - Saqib Bilal; Raheem Shahzad; Sajjad Asaf; Muhammad Imran; Ahmed Al-Harrasi; In-Jung Lee (Environmental Pollution, 2023)

Novel modeling and optimization framework for Navy Blue adsorption onto eco-friendly magnetic geopolymer composite - Hammad Khan; Sajjad Hussain; Rehman Zahoor; Muhammad Arshad; Muhammad Umar; Mohsin Ali Marwat; Adnan Khan; Javaid Rabbani Khan; Muhammad Abdul Haleem (Environmental Research, 2023)

Electrically conductive Pt-MOFs for acidic oxygen reduction: Optimized performance via altering conjugated ligands - Rashid Iqbal; Sajjad Ali; Adil Saleem; Muhammad K. Majeed; Arshad Hussain; Sajid Rauf; Abdul Rehman Akbar; Hu Xu; Liang Qiao; Wei Zhao (Chemical Engineering Journal, 2023)

WS2-embedded MXene/GO hybrid nanosheets as electrodes for asymmetric supercapacitors and hydrogen evolution reactions - Sajjad Hussain; Dhanasekaran Vikraman; Zulfqar Ali Sheikh; Muhammad Taqi Mehran; Faisal Shahzad; Khalid Mujasam Batoo; Hyun-Seok Kim; Deok-Kee Kim; Muhammad Ali; Jongwan Jung (Chemical Engineering Journal, 2023)

Chemopreventive role of probiotics against cancer: a comprehensive mechanistic review - Shehzeen Noor; Shaukat Ali; Shumaila Riaz; Iqra Sardar; Muhammad Adeel Farooq; Ayesha Sajjad (Molecular Biology Reports, 2023)

A DFT Study on New Photovoltaic Dyes to Investigate their NLO Tuning at Near Infrared Region (NIR) as Pull–push Effect by End Capped Acceptors - Abrar U. Hassan; Sajjad H. Sumrra; Muhammad F. Nazar; Cihat Güleryüz (Journal of Fluorescence, 2023)

Association mapping for abiotic stress tolerance using heat- and drought-related syntenic markers in okra - Ikhlaq Ahmad; Rashid Mehmood Rana; Mahmood Ul Hassan; Muhammad Azam Khan; Muhammad Sajjad (Molecular Biology Reports, 2022)

Genome wide association mapping of yield and various desirable agronomic traits in Rice - Muhammad Ashfaq; Abdul Rasheed; Muhammad Sajjad; Muhammad Ali; Bilal Rasool; Muhammad Arshad Javed; Sami Ul Allah; Shabnum Shaheen; Alia Anwar; Muhammad Shafiq Ahmad; Urooj Mubashar (Molecular Biology Reports, 2022)

Genetic diversity and population structure assessed through simple sequence repeat markers in Saccharum spp. hybrids from Pakistan and Sri Lanka - Sundas Shahzad; Muhammad Saeed; Shagufta Perveen; Muhammad Azeem; Iqra Sajjad; Shazia Saeed; Muhammad Naeem; Alia Javed; Iqra Sultan; Ukasha Faria; Sana Maryam; Muhammad Zaid Yousaf (Genetic Resources and Crop Evolution, 2022)

Evaluating the thermal-cooling induced effects on the Ambela granite properties (from Pakistan) using experimental and image processing techniques - Naseer Muhammad Khan; Liqiang Ma; Kewang Cao; Sajjad Hussain; Asghar Ali; Wei Liu; Saad S. Alarifi; Kausar Sultan shah; Sajid Khan; Yang Xiaoxu; Yujun Xu (Bulletin of Engineering Geology and the Environment, 2022)

Soil inorganic carbon sequestration through alkalinity regeneration using biologically induced weathering of rock powder and biochar - Muhammad Azeem; Sajjad Raza; Gang Li; Pete Smith; Yong-Guan Zhu (Soil Ecology Letters, 2022)

A comparative analysis of renewable and non-renewable energy generation to relegate CO2 emissions and general costs in household systems - Mudassar Hussain; Manzoor Sultan; Faiza Uzma; Cheng Longsheng; Muhammad Yousaf Malik; Abdul Rahman Butt; Aqsa Sajjad; Ijaz Younis; Muhammad Imran (Environmental Science and Pollution Research, 2022)

Optimization of Process Parameters in Friction Stir Welding of Aluminum 5451 in Marine Applications - Shoaib Ahmed; Rana Atta ur Rahman; Awais Awan; Sajjad Ahmad; Waseem Akram; Muhammad Amjad; Mohd Yazid Yahya; Seyed Saeid Rahimian Koloor (Journal of Marine Science and Engineering, 2022)
Friction stir welding (FSW) is one of the primary fabrication techniques for joining different components, and it has become popular, especially in aluminum alloy structures for marine applications. The welded joint with the friction stir process greatly depends on the process parameters, i.e., feed rate, rotational speed, and pin profile of the tool. In the current study, plates of aluminum 5451 alloy were joined by the FSW technique, and the Taguchi method was used to find the process parameters at an optimal level. The maximum value of tensile strength, i.e., 160.6907 MPa, was achieved using optimum welding conditions of a tool rotation speed of 1400, a feed rate of 18 mm/min, and the tool pin with threads. The maximum value of hardness, i.e., 81.056 HV, was achieved using optimum conditions of 1200 tool rotational speed and a feed rate of 18 mm/min with a tool pin profile having threads. In addition, the contribution in terms of the percentage of each input parameter was found by the analysis of variance (ANOVA). The ANOVA results revealed that the pin profile of the tool has the maximum contribution of 67.77% and 62.42% in achieving the optimum value of tensile strength and hardness, respectively. The study also investigated the joint efficiency of the friction stir welded joint, hardness at the weld zone, and metallography on FSW samples at the optimized level. The effectiveness and reliability of FSW joints for shipping industry applications can be observed by joint efficiency. That was investigated at optimum conditions, and it comes out to be 80.5%.

RETRACTED ARTICLE: Ameliorative effect of two structurally divergent hydrazide derivatives against DSS-induced colitis by targeting Nrf2 and NF-κB signaling in mice - Ashrafullah Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Sajjad Ahmad; Muhammad Usman Amin; Muhammad Naeem Ahmed; Zia-ur-Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Exploring thiazole-linked thioureas using alkaline phosphatase assay, biochemical evaluation, computational analysis and structure–activity relationship (SAR) studies - Sajid Ali Channar; Pervaiz Ali Channar; Aamer Saeed; Aisha A. Alsfouk; Syeda Abida Ejaz; Rabail Ujan; Razia Noor; Muhammad Sajjad Bilal; Qamar Abbas; Zahid Hussain; Bilal Ahmad Khan; Hussain Raza; et al. (Medicinal Chemistry Research, 2022)

Acceleration of flow modeling using a freeware 2D GPU-shallow water equations code - Prince Mahmood; Sajjad Haider; Hamza Farooq Gabriel; Muhammad Shahid; Zain Syed (Arabian Journal of Geosciences, 2022)

Investigating feasible sites for multi-purpose small dams in Swat District of Khyber Pakhtunkhwa Province, Pakistan: socioeconomic and environmental considerations - Anwar Hussain; Khalil Ur Rahman; Muhammad Shahid; Sajjad Haider; Quoc Bao Pham; Nguyen Thi Thuy Linh; Saad Shauket Sammen (Environment, Development and Sustainability, 2022)

Effect of forage to concentrate ratio on growth performance and feeding behavior of Thalli lambs - Muhammad Farhan Ayaz Chishti; Muhammad Aziz ur Rahman; Karamo Jatta; Sajjad Khan; Muhammad Riaz; Qamar Bilal; Urooj Anwar; Sibtain Ahmad; Hassan Munir Bajwa; Fahd Rasul (Tropical Animal Health and Production, 2022)

Does energy use and economic growth allow for environmental sustainability? An empirical analysis of Pakistan - Muhammad Mohsin; Sobia Naseem; Muddassar Sarfraz; Muhammad Zia-UR-Rehman; Sajjad Ahmad Baig (Environmental Science and Pollution Research, 2022)

Geological mapping and neo-tectonics studies of the eocene limestone distributed over Mala Khel Anticline, Trans Indus ranges, North-West Himalayas, Pakistan - Nazir-ur- Rehman; Sajjad Ahmad; Shah Faisal; Asghar Ali; Muhammad Waqar Azeem; Afrasiab; Shuja Ullah; Salik Javed (Arabian Journal of Geosciences, 2022)

Assessment of land use/land cover changes and its effect on land surface temperature using remote sensing techniques in Southern Punjab, Pakistan - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Hamid Majeed; Saeed Ahmad Qaisrani; Hafiz Mohkum Hammad; Muhammad Amjad; Iftikhar Ahmad; Shah Fahad; Naveed Ahmad; Wajid Nasim (Environmental Science and Pollution Research, 2022)

Genetic diversity and marker trait association for phytophthora resistance in chilli - Tazien Bukhari; Rashid Mehmood Rana; Mahmood Ul Hassan; Farah Naz; Muhammad Sajjad (Molecular Biology Reports, 2022)

Monitoring land use land cover changes and its impacts on land surface temperature over Mardan and Charsadda Districts, Khyber Pakhtunkhwa (KP), Pakistan - Rehan Khan; Huan Li; Muhammad Basir; Yuan Lin Chen; Meer Muhammad Sajjad; Ihtisham Ul Haq; Barkat Ullah; Muhammad Arif; Waqas Hassan (Environmental Monitoring and Assessment, 2022)

Phosphate solubilizing epilithic and endolithic bacteria isolated from clastic sedimentary rocks, Murree lower Himalaya, Pakistan - Imran Khan; Sahib Zada; Muhammad Rafiq; Wasim Sajjad; Sumayya Zaman; Fariha Hasan (Archives of Microbiology, 2022)

Fertigation of calcium nitrate [Ca(NO3)2] confers metal tolerance in two chickpea (Cicer arietinum L.) cultivars - Abida Parveen; Iqbal Hussain; Shagufta Perveen; Muhammad Arslan Ashraf; Rizwan Rasheed; Saddam Hussain; Sajjad Hussain; Sumaira Thind; Arshad Ali; Zahid Ullah; Qaisar Mahmood (Arabian Journal of Geosciences, 2022)

Volkamer Lemon Tetraploid Rootstock Transmits the Salt Tolerance When Grafted with Diploid Kinnow Mandarin by Strong Antioxidant Defense Mechanism and Efficient Osmotic Adjustment - Muhammad Fasih Khalid; Raphael Morillon; Muhammad Akbar Anjum; Shaghef Ejaz; Muhammad Junaid Rao; Shakeel Ahmad; Sajjad Hussain (Journal of Plant Growth Regulation, 2022)

Different sources of irrigation water affect heavy metal accumulation in soils and some properties of guava fruits - Sajjad Hussain; Ahmad Hassan; Pakiza Arshad; Muhammad Akbar Anjum (Environmental Science and Pollution Research, 2022)

ICT, renewable energy, financial development, and CO2 emissions in developing countries of East and South Asia - Zakia Batool; Syed Muhammad Faraz Raza; Sajjad Ali; Syed Zain Ul Abidin (Environmental Science and Pollution Research, 2022)

Effects of Ferula asafetida, closantel, albendazole, oxfendazole, and ivermectin against Haemonchus contortus in goats and sheep - Abdul Jabbar; Muhammad Zahid Iqbal; Muhammad Ashraf; Aneela Zameer Durrani; Hira Sajjad; Mohammed Nasiru Wana; Asad Ullah; Muhammad Imran; Muhammad Shair Zaman Ghauri; Hafiz Ishfaq Ahmad (Tropical Animal Health and Production, 2022)

Correction to: Antioxidant and antibacterial activities of Artemisia absinthium and Citrus paradisi extracts repress viability of aggressive liver cancer cell line - Muhammad Ali; Rida Iqbal; Muhammad Safdar; Sehrish Murtaza; Ghulam Mustafa; Muhammad Sajjad; Shazia Anwer Bukhari; Tayyaba Huma (Molecular Biology Reports, 2022)

Drought-tolerant Bacillus megaterium isolated from semi-arid conditions induces systemic tolerance of wheat under drought conditions - Urooj Rashid; Humaira Yasmin; Muhammad Nadeem Hassan; Rabia Naz; Asia Nosheen; Muhammad Sajjad; Noshin Ilyas; Rumana Keyani; Zahra Jabeen; Saqib Mumtaz; Mohammed Nasser Alyemeni; Parvaiz Ahmad (Plant Cell Reports, 2022)

A sustainable generalization of inverse Lindley distribution for wind speed analysis in certain regions of Pakistan - Muhammad Shoaib; Irum Sajjad Dar; Muhammad Ahsan-ul-Haq; Rana Muhammad Usman (Modeling Earth Systems and Environment, 2022)

Genetic dissection of grain yield traits in a large collection of spring wheat (Triticum aestivum L.) germplasm - Sultan Habibullah Khan; Muhammad Sajjad; Saima Gulnaz; Sundas Waqar; Munawar Shahzad; Saima Mir Arain (Journal of Crop Science and Biotechnology, 2022)

Recycling of ceramic tiles waste and marble waste in sustainable production of concrete: a review - Sajjad Ali Mangi; Muhammad Saleem Raza; Shabir Hussain Khahro; Abdul Sami Qureshi; Rabinder Kumar (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Impact of credit, liquidity, and systematic risk on financial structure: comparative investigation from sustainable production - Muhammad Sadiq; Sami Alajlani; Muhammed Sajjad Hussain; Rashid Ahmad; Furrukh Bashir; Supat Chupradit (Environmental Science and Pollution Research, 2022)

Biochemical resistance characterization to chlorpyrifos, acetamiprid, spinosad, and emamectin benzoate in Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) from Pakistan - Bushra Saddiq; Muhammad Babar Shahzad Afzal; Ashfaq Ahmad Sial; Naeem Abbas; Sarfraz Ali Shad; Asif Sajjad; Sajjad Ali (Phytoparasitica, 2022)

Characterization of new COBRA like (COBL) genes in wheat (Triticum aestivum) and their expression analysis under drought stress - Muhammad Zaheer; Shoaib Ur Rehman; Sultan Habibullah Khan; Shahmeer Shahid; Awais Rasheed; Rabia Naz; Muhammad Sajjad (Molecular Biology Reports, 2022)

New organosulfur metallic compounds as potent drugs: synthesis, molecular modeling, spectral, antimicrobial, drug likeness and DFT analysis - Abrar Ul Hassan; Sajjad Hussain Sumrra; Muhammad Nadeem Zafar; Muhammad Faizan Nazar; Ehsan Ullah Mughal; Muhammad Naveed Zafar; Mazhar Iqbal (Molecular Diversity, 2022)

Genotypic Differences Among the Rice Genotypes to Arsenic Stress Cultivated Under Two Water Regimes: With an Inference to Human Health - Hafiz Faiq Bakhat; Sidra Arshad; Natasha; Sunaina Abbas; Ghulam Mustafa Shah; Shah Fahad; Hafiz Mohkum Hammad; Muhammad Sajjad; Muhammad Ashfaq; Muhammad Shahid (Journal of Plant Growth Regulation, 2022)

Comparative seismic performance assessment of RC and RC/ECC hybrid frame structures: a shake table study - Fasih Ahmed Khan; Muhammad Rashid; Sajjad Wali Khan; Muhammad Rizwan; Yasir Irfan Badrashi; Muhammad Fahim; Muhammad Ashraf Tanoli; Wasim Khaliq; Akhtar Gul (Innovative Infrastructure Solutions, 2022)

The influence of energy consumption and economic growth on environmental degradation in BRICS countries: an application of the ARDL model and decoupling index - Sobia Naseem; Muhammad Mohsin; Muhammad Zia-UR-Rehman; Sajjad Ahmad Baig; Muddassar Sarfraz (Environmental Science and Pollution Research, 2022)

Infrared radiation characteristics based rock failure indicator index for acidic mudstone under uniaxial loading - Naseer Muhammad Khan; Liqiang Ma; Kewang Cao; Sajjad Hussain; Wei Liu; Yujun Xu (Arabian Journal of Geosciences, 2022)

A Review of Antimicrobial Peptides: Its Function, Mode of Action and Therapeutic Potential - Sehrish Nayab; Muhammad Aamir Aslam; Sajjad ur Rahman; Zia ud Din Sindhu; Sanaullah Sajid; Nishat Zafar; Maida Razaq; Rabia Kanwar; Amanullah (International Journal of Peptide Research and Therapeutics, 2022)

The effect of GnRH administration/insemination time on follicular growth rate, ovulation intervals, and conception rate of Nili Ravi buffalo heifers in 7 –day-CIDR Co-synch - Sajjad Haider; Ghazanfar Ali Chishti; Muhammad Usman Mehmood; Muhammad Ameen Jamal; Khalid Mehmood; Muhammad Shahzad; Muhammad Zahid Tahir (Tropical Animal Health and Production, 2021)

Antioxidant and antibacterial activities of Artemisia absinthium and Citrus paradisi extracts repress viability of aggressive liver cancer cell line - Muhammad Ali; Rida Iqbal; Muhammad Safdar; Sehrish Murtaza; Ghulam Mustafa; Muhammad Sajjad; Shazia Anwer Bukhari; Tayyaba Huma (Molecular Biology Reports, 2021)

Hydrogen Sulfide: A Novel Gaseous Molecule for Plant Adaptation to Stress - Mukhtar Ahmed; Shah Fahad; Muhammad Arif Ali; Sajjad Hussain; Muhammad Tariq; Fariha Ilyas; Shakeel Ahmad; Shah Saud; Hafiz Mohkum Hammad; Wajid Nasim; Chao Wu; Hongyan Liu (Journal of Plant Growth Regulation, 2021)

Hydrogeochemical and health risk investigation of potentially toxic elements in groundwater along River Sutlej floodplain in Punjab, Pakistan - Sajjad Ahmad; Muhammad Imran; Behzad Murtaza; Natasha; Muhammad Arshad; Rab Nawaz; Abdul Waheed; Hafiz Mohkum Hammad; Muhammad Asif Naeem; Muhammad Shahid; Nabeel Khan Niazi (Environmental Geochemistry and Health, 2021)

Facile synthesis, spectroscopic evaluation and antimicrobial screening of metal endowed triazole compounds - Sajjad H. Sumrra; Wardha Zafar; Hassan Javed; Muddassar Zafar; Muhammad Z. Hussain; Muhammad Imran; Muhammad A. Nadeem (BioMetals, 2021)

Using space–time scan statistic for studying the effects of COVID-19 in Punjab, Pakistan: a guideline for policy measures in regional agriculture - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Shah Fahad; Wajid Nasim; Hafiz Mohkum Hammad; Ghulam Mustafa Shah; Behzad Murtaza; Muhammad Tahir; Saima Parveen (Environmental Science and Pollution Research, 2021)

SNPs at 3′UTR of APOL1 and miR-6741-3p target sites associated with kidney diseases more susceptible to SARS-COV-2 infection: in silco and in vitro studies - Muhammad Safdar; Muhammad Sajjad Khan; Abdulkarim Yasin Karim; Shwan Ali Omar; Shukur Wasman Smail; Muhammad Saeed; Sana Zaheer; Mazhar Ali; Bilal Ahmad; Muhammad Tasleem; Yasmeen Junejo (Mammalian Genome, 2021)

Evaluating the suitability of two parametric wind speed distributions: a case study from Pakistan - Muhammad Ahsan ul Haq; Sohail Chand; Muhammad Zahir Sajjad; Rana Muhammad Usman (Modeling Earth Systems and Environment, 2021)

The influence of personality traits on sustainability-oriented entrepreneurial intentions: the moderating role of servant leadership - Sajjad Nawaz Khan; Muhammad Mubushar; Ikram Ullah Khan; Hafiz Mudassir Rehman; Safeer Ullah Khan (Environment, Development and Sustainability, 2021)

Prediction of an early failure point using infrared radiation characteristics and energy evolution for sandstone with different water contents - Naseer Muhammad Khan; Liqiang Ma; Kewang Cao; Sajjad Hussain; Wei Liu; Yujun Xu; Qiupeng Yuan; Jie Gu (Bulletin of Engineering Geology and the Environment, 2021)

Origin, Pathogenesis, Diagnosis and Treatment Options for SARS-CoV-2: A Review - Humna Sajjad; Mohsin Majeed; Saiqa Imtiaz; Mariyam Siddiqah; Anila Sajjad; Misbahud Din; Muhammad Ali (Biologia, 2021)

Assessing the potential and hydrological usefulness of the CHIRPS precipitation dataset over a complex topography in Pakistan - Muhammad Shahid; Khalil Ur Rahman; Sajjad Haider; Hamza Farooq Gabriel; Abdul Jabbar Khan; Quoc Bao Pham; Babak Mohammadi; Nguyen Thi Thuy Linh; Duong Tran Anh (Hydrological Sciences Journal, 2021)

The combined effect of climatic factors and technical advancement on yield of sugarcane by using ARDL approach: evidence from Pakistan - Sajjad Ali; Muhammad Zubair; Sadeed Hussain (Environmental Science and Pollution Research, 2021)

Exploring genetic diversity and population structure of Punjab goat breeds using Illumina 50 K SNP bead chip - Raja Danish Muner; Muhammad Moaeen-ud-Din; Ghulam Bilal; Hafiz Muhammad Waheed; Muhammad Sajjad Khan; Muhammad Javaid Asad; Zulfiqar Hussain Kuthu (Tropical Animal Health and Production, 2021)

Menadione sodium bisulfite alleviated chromium effects on wheat by regulating oxidative defense, chromium speciation, and ion homeostasis - Sajjad Hassan Askari; Muhammad Arslan Ashraf; Shafaqat Ali; Muhammad Rizwan; Rizwan Rasheed (Environmental Science and Pollution Research, 2021)

Co-movement of energy prices and stock market return: environmental wavelet nexus of COVID-19 pandemic from the USA, Europe, and China - FengSheng Chien; Muhammad Sadiq; Hafiz Waqas Kamran; Muhammad Atif Nawaz; Muhammed Sajjad Hussain; Muhammad Raza (Environmental Science and Pollution Research, 2021)

Metals Distribution, Histopathological Alterations, and Health Risk Assessment in Different Tissues of Fish (Ctenopharyngodon idella) - Nazish Shah; Muhammad Khisroon; Said Sajjad Ali Shah (Biological Trace Element Research, 2021)

Epidemiology of molecular probes in Xpert MTB/RIF assay in Khyber Pakhtunkhwa, Pakistan - Anwar Sheed Khan; Muhammad Tahir Khan; Sajid Ali; Taj Ali Khan; Muhammad Qasim; Arif Malik; Sajid Ali; Wasim Sajjad; Qurrat ul ain; Muhammad Irfan (Archives of Microbiology, 2021)

Parameter estimation of the Pareto distribution using least squares approaches blended with different rank methods and its applications in modeling natural catastrophes - Shahzad Hussain; Sajjad Haider Bhatti; Tanvir Ahmad; Muhammad Ahmed Shehzad (Natural Hazards, 2021)

Effect of green human resource management practices on organizational sustainability: the mediating role of environmental and employee performance - Fiza Amjad; Waseem Abbas; Muhammad Zia-UR-Rehman; Sajjad Ahmad Baig; Muhammad Hashim; Ayesha Khan; Hakeem-ur- Rehman (Environmental Science and Pollution Research, 2021)

Distribution and health risk assessment of trace elements in ground/surface water of Kot Addu, Punjab, Pakistan: a multivariate analysis - Zafar Abbas; Muhammad Imran; Natasha Natasha; Behzad Murtaza; Muhammad Amjad; Noor Samad Shah; Zia Ul Haq Khan; Iftikhar Ahmad; Sajjad Ahmad (Environmental Monitoring and Assessment, 2021)

Late Cretaceous pelagic laminites at the northwestern margin of Indian plate, Pakistan: implications for basin bathymetry and ophiolite emplacement - Sajjad Ahmad; Suleman Khan; Bilal Wadood; Asad Naseer; Muhammad Noman; Jamal Wadood; Muhammad Muslim (Carbonates and Evaporites, 2021)

Molecular cloning and characterization of three CoIDA genes in Camellia oleifera - Mi Yang; Xiao Hu; Xiang Ouyang; Muhammad Sajjad; Xiaoling Ma; Deyi Yuan (Brazilian Journal of Botany, 2021)

Effect of milk or milk replacer offered at varying levels on growth performance of Friesian veal calves - Muhammad Khalid Qadeer; Shaukat Ali Bhatti; Haq Nawaz; Muhammad Sajjad Khan (Tropical Animal Health and Production, 2021)

RETRACTED ARTICLE: The step towards environmental mitigation in Pakistan: do transportation services, urbanization, and financial development matter? - Danish Iqbal Godil; Paiman Ahmad; Muhammad Sajjad Ashraf; Salman Sarwat; Arshian Sharif; Syed Shabib-ul-Hasan; Kittisak Jermsittiparsert (Environmental Science and Pollution Research, 2021)

Growth and Physiology of Maize (Zea mays L.) in a Nickel-Contaminated Soil and Phytoremediation Efficiency Using EDTA - Muhammad Imran Tipu; Muhammad Yasin Ashraf; Nadeem Sarwar; Muhammad Akhtar; Muhammad Rashid Shaheen; Sajjad Ali; Christos A. Damalas (Journal of Plant Growth Regulation, 2021)

Assessing the efficiency and total factor productivity growth of the banking industry: do environmental concerns matters? - Faluk Shair; Sun Shaorong; Hafiz Waqas Kamran; Muhammed Sajjad Hussain; Muhammad Atif Nawaz; Van Chien Nguyen (Environmental Science and Pollution Research, 2021)

Trilemma association of energy consumption, carbon emission, and economic growth of BRICS and OECD regions: quantile regression estimation - Muhammad Atif Nawaz; Muhammed Sajjad Hussain; Hafiz Waqas Kamran; Syed Ehsanullah; Rida Maheen; Faluk Shair (Environmental Science and Pollution Research, 2021)

Remote Sensing of Narrowing Barrier Islands along the Coast of Pakistan over Past 30 Years - Shamsa Kanwal; Xiaoli Ding; Muhammad Sajjad; Majid Nazeer; Ibrahim Zia (Journal of Marine Science and Engineering, 2021)
Barrier islands (BIs) are the first line of defense against the sea/wave actions in coastal areas, and assessing their stability is crucial in the context of effective coastal planning. Therefore, this study evaluates the spatial–temporal shoreline changes of the BIs in Pakistan over the past three decades (1989–2018). Satellite data from Landsat missions are used to delineate the shorelines of 19 BIs in Pakistan. After delineating the shorelines from satellite observations, two well-known statistical methods (i.e., end point rate (EPR) and linear regression rate (LRR)) are used to capture the localized changes in the BIs. The results ascertain that nearly all of the BIs have experienced noteworthy erosion during the past three decades. While the mean erosion over all the BIs during the study period is estimated to be >6 m/y, significant spatial heterogeneities among the individual BIs exist. The interdecadal comparison indicates that the highest mean erosion of the BIs occurred during the period 1989–1999 (13.03 ± 0.62 m/y), which gradually reduced over the preceding decades (i.e., 7.76 ± 0.62 m/y during the period 1999–2009 and 3.8 ± 0.7 m/y during the period 2009–2018). Nevertheless, ~65% of the total BIs experienced high erosion (>2 m/y), ~15% experienced moderate (

Optimizing Phosphorus Levels in Wheat Grown in a Calcareous Soil with the Use of Adsorption Isotherm Models - Muhammad Farhan Saeed; Aftab Jamal; Dost Muhammad; Ghulam Mustafa Shah; Hafiz Faiq Bakhat; Iftikhar Ahmad; Sajjad Ali; Fahid Ihsan; Jingkuan Wang (Journal of Soil Science and Plant Nutrition, 2021)

Mortality effects of hypercapnia in modified atmospheres on larval and adult stages of red flour beetle Tribolium castaneum (Herbst) - Zahid Mahmood Sarwar; Nishat Fatima; Muhammad Sajjad (International Journal of Tropical Insect Science, 2021)

Application of precipitation products for flood modeling of transboundary river basin: a case study of Jhelum Basin - Muhammad Umer; Hamza Farooq Gabriel; Sajjad Haider; Ammara Nusrat; Muhammad Shahid; Muhammad Umer (Theoretical and Applied Climatology, 2021)

Role of fruit volatiles of different guava varieties in attraction and oviposition behaviors of peach fruit fly, Bactrocera zonata Saunders - Muhammad Binyameen; Abdul Hamid; Imran Afzal; Muhammad Sajjad; Muhammad Azeem; Syed Muhammad Zaka; Zahid Mehmood Sarwar; Sarfraz Ali Shad; Thomas C. Baker; Fredrik Schlyter (Arthropod-Plant Interactions, 2021)

Tectonic evolution, prospectivity and structural studies of the hanging wall of Main Boundary Thrust along Akhurwal-Kohat transect, Khyber Pakhtunkhwa: implications for future exploration - Muhammad Yaseen; Sohail Wahid; Sajjad Ahmad; Gohar Rehman; Jawad Ahmad; Muhammad Naveed Anjum; Mubashir Mehmood (Arabian Journal of Geosciences, 2021)

Modulation of sugar and nitrogen in callus induction media alter PAL pathway, SA and biomass accumulation in rice callus - Rahmatullah Jan; Muhammad Aaqil Khan; Sajjad Asaf; In-Jung Lee; Kyung-Min Kim (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

The sedimentological and stratigraphical analysis of the Paleocene to Early Eocene Dungan Formation, Kirthar Fold and Thrust Belt, Pakistan: implications for reservoir potential - Sajjad Ahmad; Bilal Wadood; Suleman Khan; Abd Ullah; Ghazi Mustafa; Muhammad Hanif; Hasbee Ullah (Journal of Sedimentary Environments, 2020)

Management of Tribolium castaneum using synergism between conventional fumigant and plant essential oils - Abdul Khaliq; Muhammad Irfan Ullah; Muhammad Afzal; Sajjad Ali; Asif Sajjad; Akhlaq Ahmad; Samina Khalid (International Journal of Tropical Insect Science, 2020)

Sowing Date and Hybrid Choice Matters Production of Maize–Maize System - Ghulam Abbas; Shakeel Ahmad; Mubshar Hussain; Zartash Fatima; Sajjad Hussain; Pakeeza Iqbal; Mukhtar Ahmed; Muhammad Farooq (International Journal of Plant Production, 2020)

TaCKX gene family, at large, is associated with thousand-grain weight and plant height in common wheat - Muhammad Shoaib; Wenlong Yang; Qiangqiang Shan; Linhe Sun; Dongzhi Wang; Muhammad Sajjad; Xin Li; Jiazhu Sun; Dongcheng Liu; Kehui Zhan; Aimin Zhang (Theoretical and Applied Genetics, 2020)

Environmental concerns and switching toward electric vehicles: geographic and institutional perspectives - Aqsa Sajjad; Fahad Asmi; Jianxun Chu; Muhammad Azfar Anwar (Environmental Science and Pollution Research, 2020)

Using GIS tools to detect the land use/land cover changes during forty years in Lodhran District of Pakistan - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Waseem Akram; Hafiz Mohkum Hammad; Mazhar Ali; Nasir Masood; Asad Amin; Hafiz Umar Farid; Syeda Refat Sultana; Shah Fahad; Depeng Wang; et al. (Environmental Science and Pollution Research, 2020)

Proposed Definition of Experimental Secondary Ischemia for Mouse Subarachnoid Hemorrhage - Jasper Hans van Lieshout; Serge Marbacher; Sajjad Muhammad; Hieronymus D. Boogaarts; Ronald H. M. A. Bartels; Maxine Dibué; Hans-Jakob Steiger; Daniel Hänggi; Marcel A. Kamp (Translational Stroke Research, 2020)
Inconsistency in outcome parameters for delayed cerebral ischemia (DCI) makes it difficult to compare results between mouse studies, in the same way inconsistency in outcome parameters in human studies has for long obstructed adequate comparison. The absence of an established definition may in part be responsible for the failed translational results. The present article proposes a standardized definition for DCI in experimental mouse models, which can be used as outcome measure in future animal studies. We used a consensus-building approach to propose a definition for “experimental secondary ischemia” (ESI) in experimental mouse subarachnoid hemorrhage that can be used as an outcome measure in preclinical studies. We propose that the outcome measure should be as follows: occurrence of focal neurological impairment or a general neurological impairment compared with a control group and that neurological impairment should occur secondarily following subarachnoid hemorrhage (SAH) induction compared with an initial assessment following SAH induction. ESI should not be used if the condition can be explained by general anesthesia or if other means of assessments sufficiently explain function impairment. If neurological impairment cannot reliably be evaluated, due to scientific setup. Verification of a significant secondary impairment of the cerebral perfusion compared with a control group is mandatory. This requires longitudinal examination in the same animal. The primary aim is that ESI should be distinguished from intervention-related ischemia or neurological deficits, in order establish a uniform definition for experimental SAH in mice that is in alignment with outcome measures in human studies.

Integrated Application of Organic Amendments with Alcaligenes sp. AZ9 Improves Nutrient Uptake and Yield of Maize (Zea mays) - Azhar Hussain; Maqshoof Ahmad; Muhammad Zahid Mumtaz; Sajjad Ali; Rubab Sarfraz; Muhammad Naveed; Moazzam Jamil; Christos A. Damalas (Journal of Plant Growth Regulation, 2020)

Selection criteria for yield potential in a large collection of Vigna radiata (L.) accessions - Ayesha Tahir; Muhammad Kashif Ilyas; Muhammad Muddassir Sardar; Ali Kiani Pouya; Fatemeh Rasouli; Ameer Bibi; Zahra Jabeen; Muhammad Sajjad; Sadar Uddin Siddiqui; Abdul Ghafoor (Euphytica, 2020)

Performance evaluation of conventional and hybrid woven fabrics for the development of sustainable personal protective clothing - Arshad Hussain Memon; Mazhar Hussain Peerzada; Khan Muhammad Brohi; Sheeraz Ahmed Memon; Sajjad Ali Mangi (Environmental Science and Pollution Research, 2020)

Assessment of copper, chromium, and lead toxicity in fish (Ctenopharyngodon idella Valenciennes, 1844) through hematological biomarkers - Nazish Shah; Muhammad Khisroon; Said Sajjad Ali Shah (Environmental Science and Pollution Research, 2020)

HPLC-UV characterization, anticholinesterase, and free radical-scavenging activities of Rosa moschata Herrm. leaves and fruits methanolic extracts - Nausheen Nazir; Atif Ali Khan Khalil; Mohammad Nisar; Muhammad Zahoor; Sajjad Ahmad (Brazilian Journal of Botany, 2020)

Characterization and synthetic biology of lipase from Bacillus amyloliquefaciens strain - Muhammad Tahir Khan; Aman Chandra Kaushik; Qurrat ul ain Rana; Shaukat Iqbal Malik; Anwar Sheed Khan; Dong-Qing Wei; Wasim Sajjad; Shabir Ahmad; Sajid Ali; Ameenullah; Muhammad Irfan (Archives of Microbiology, 2020)

Toxicity evaluation of pesticide chlorpyrifos in male Japanese quails (Coturnix japonica) - Suliman; Ajmal Khan; Syed Sajjad Ali Shah; Naila Gulfam; Muhammad Khisroon; Muhammad Zahoor (Environmental Science and Pollution Research, 2020)

Human Biomonitoring of Trace Elements in Scalp Hair from Healthy Population of Pakistan - Fouzia Noreen; Ashif Sajjad; Khalid Mahmood; Muhammad Anwar; Manzar Zahra; Amir Waseem (Biological Trace Element Research, 2020)

Pigment production by cold-adapted bacteria and fungi: colorful tale of cryosphere with wide range applications - Wasim Sajjad; Ghufranud Din; Muhammad Rafiq; Awais Iqbal; Suliman Khan; Sahib Zada; Barkat Ali; Shichang Kang (Extremophiles, 2020)

2D numerical modeling of two dam-break flood model studies in an urban locality - Sajjad Haider; Umer Saeed; Muhammad Shahid (Arabian Journal of Geosciences, 2020)

Synthesis, characterization, and biocompatibility of lanthanum titanate nanoparticles in albino mice in a sex-specific manner - Irum Naz Akram; Sana Akhtar; Ghulam Khadija; Mian Muhammad Awais; Muhammad Latif; Aasia Noreen; Mehwish Mobeen; Fareeha Sajjad; Zahida Sardar; Shahid Iqbal; Muhammad Naeem Ashiq; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Extracting mass concentration time series features for classification of indoor and outdoor atmospheric particulates - Lal Hussain; Wajid Aziz; Sharjil Saeed; Muhammad Rafique; Malik Sajjad Ahmed Nadeem; Seong-O Shim; Sania Aftar; Jawad-ur-Rehman Pirzada (Acta Geophysica, 2020)

Post-translational regulation of plasma membrane H+-ATPase is involved in the release of biological nitrification inhibitors from sorghum roots - Muhammad Rahil Afzal; Maoxing Zhang; Heyu Jin; Genmei Wang; Mingchao Zhang; Ming Ding; Sajjad Raza; Jun Hu; Houqing Zeng; Xiang Gao; Guntur Venkata Subbarao; Yiyong Zhu (Plant and Soil, 2020)

Nephroprotective effects of curcumin loaded chitosan nanoparticles in cypermethrin induced renal toxicity in rabbits - Maira Anwar; Faqir Muhammad; Bushra Akhtar; Sajjad ur Rehman; Muhammad Kashif Saleemi (Environmental Science and Pollution Research, 2020)

Effect of biochar and phosphate solubilizing bacteria on growth and phosphorus uptake by maize in an Aridisol - Muhammad Arif Ali; Muhammad Mustansar Ajaz; Muhammad Rizwan; Muhammad Farooq Qayyum; Muhammad Arshad; Sajjad Hussain; Niaz Ahmad; Muhammad Amjad Qureshi (Arabian Journal of Geosciences, 2020)

Transcriptomic analysis of root specific drought mediated response of G. arboreum and G. hirsutum - Zarnab Ahmad; Sajjad Sadique; Muhammad B. Sarwar; Bushra Rashid; Sameera Hassan; Sultana Rasheed; Khurram Bashir; Motoaki Seki; Tayyab Husnain (Biologia, 2020)

Characterization of phenolic compounds in two novel lines of Pisum sativum L. along with their in vitro antioxidant potential - Nausheen Nazir; Mohammad Nisar; Sajjad Ahmad; Syed Fazal Wadood; Tour Jan; Muhammad Zahoor; Manzoor Ahmad; Abid Ullah (Environmental Science and Pollution Research, 2020)

Study of land cover/land use changes using RS and GIS: a case study of Multan district, Pakistan - Sajjad Hussain; Muhammad Mubeen; Waseem Akram; Ashfaq Ahmad; Muhammad Habib-ur-Rahman; Abdul Ghaffar; Asad Amin; Muhammad Awais; Hafiz Umar Farid; Amjad Farooq; Wajid Nasim (Environmental Monitoring and Assessment, 2020)

Reservoir Inflow Prediction by Ensembling Wavelet and Bootstrap Techniques to Multiple Linear Regression Model - Adnan Bashir; Muhammad Ahmed Shehzad; Ijaz Hussain; Muhammad Ishaq Asif Rehmani; Sajjad Haider Bhatti (Water Resources Management, 2019)

Effect of Methyl Jasmonate and Salicylic Acid on In Vitro Growth, Stevioside Production, and Oxidative Defense System in Stevia rebaudiana - Sajjad Moharramnejad; Amirali Taheri Azam; Jaber Panahandeh; Zahra Dehghanian; Muhammad Ashraf (Sugar Tech, 2019)

Climate change communication as political agenda and voters’ behavior - Muhammad Azfar Anwar; Rongting Zhou; Aqsa Sajjad; Fahad Asmi (Environmental Science and Pollution Research, 2019)

Virulence-associated genes and antimicrobial resistance among avian pathogenic Escherichia coli from colibacillosis affected broilers in Pakistan - Mariya Azam; Mashkoor Mohsin; Sajjad-ur-Rahman; Muhammad Kashif Saleemi (Tropical Animal Health and Production, 2019)

Heavy metal exposure through artificial diet reduces growth and survival of Spodoptera litura (Lepidoptera: Noctuidae) - Sajjad Ali; Muhammad Irfan Ullah; Muhammad Farhan Saeed; Samina Khalid; Muhammad Saqib; Muhammad Arshad; Muhammad Afzal; Christos A. Damalas (Environmental Science and Pollution Research, 2019)

Role of phosphorous mining in mobilization and bioaccessibility of heavy metals in soil-plant system: Abbottabad, Pakistan - Afshan; Sajjad Ahmad; Muhammad Imran; Rab Nawaz; Muhammad Arshad; Muhammad Ejaz Ul Islam Dar; Muhammad Hussnain Siddque; Muhammad Nadeem; Liaqat Ali (Arabian Journal of Geosciences, 2019)

Growth-promoting bioactivities of Bipolaris sp. CSL-1 isolated from Cannabis sativa suggest a distinctive role in modifying host plant phenotypic plasticity and functions - Lubna; Sajjad Asaf; Abdul Latif Khan; Muhammad Waqas; Sang-Mo Kang; Muhammad Hamayun; In-Jung Lee; Anwar Hussain (Acta Physiologiae Plantarum, 2019)

Assessment of Circulating Biochemical Markers in Mice Receiving Cinnamon and Glycyrrhizin Under Carbon Tetrachloride Induced Hepatic Injury - Mahmood Rasool; Arif Malik; Sadia Saleem; Shakeel Ahmed Ansari; Javed Iqbal; Muhammad Asif; Mohammed Amjad Kamal; Mohammed Hussain Al-Qahtani; Sajjad Karim (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Folate-Functionalized Thiomeric Nanoparticles for Enhanced Docetaxel Cytotoxicity and Improved Oral Bioavailability - Muhammad Sajjad; Muhammad Imran Khan; Sara Naveed; Sana Ijaz; Omer Salman Qureshi; Syed Atif Raza; Gul Shahnaz; Muhammad Farhan Sohail (AAPS PharmSciTech, 2019)

Isolation and characterization of bacteria associated with the rhizosphere of halophytes (Salsola stocksii and Atriplex amnicola) for production of hydrolytic enzymes - Salma Mukhtar; Samina Mehnaz; Muhammad Sajjad Mirza; Kauser Abdulla Malik (Brazilian Journal of Microbiology, 2019)

Halo-tolerant rhizospheric Arthrobacter woluwensis AK1 mitigates salt stress and induces physio-hormonal changes and expression of GmST1 and GmLAX3 in soybean - Muhammad Aaqil Khan; Ihsan Ullah; Muhammad Waqas; Muhammad Hamayun; Abdul Latif Khan; Sajjad Asaf; Sang-Mo Kang; Kyung-Min Kim; Rahmatullah Jan; In-Jung Lee (Symbiosis, 2019)

Endophytic fungus Paecilomyces formosus LHL10 produces sester-terpenoid YW3548 and cyclic peptide that inhibit urease and α-glucosidase enzyme activities - Saqib Bilal; Liaqat Ali; Abdul Latif Khan; Raheem Shahzad; Sajjad Asaf; Muhammad Imran; Sang-Mo Kang; Sang-Kuk Kim; In-Jung Lee (Archives of Microbiology, 2018)

Experimental and numerical investigations for optimal emitter spacing in drip irrigation - Abdul Razzaq Ghumman; Muhammad Iqbal; Sajjad Ahmed; Hashim Nisar Hashmi (Irrigation and Drainage, 2018)
With the goal of determining optimal emitter spacing in drip irrigation, experiments were performed to examine the effects of emitter discharge on the wetted perimeter and spacing of emitters. Four types of soils were investigated using emitter discharge of 1.0, 2.0, 3.0 and 4.0 l h −1 . Wetting diameter was measured at six equal time intervals of water application. An equal volume of water was applied. After 1 h of supply of water, wetted soil was cut to observe the maximum wetted width and depth. Wet soil samples were taken from every patch of 10 × 10 cm to find the percentage of moisture by the gravimetric method. Empirical equations were developed for wetted depth and radius. Additional experiments with emitter discharge of 1–18 l h −1 were performed in sandy loam to obtain more data for accurate estimation of the coefficients of the empirical equations. Two computer programs based on trial and error and the generalized reduced‐gradient non‐linear‐optimized technique were used to find values of the coefficients. Root mean square error between the measured and simulated wetted radius and depth was minimized in optimization. Optimal emitter spacing for each type of soil was determined from the recorded data, which was found to be 35, 40, 40 and 45 cm in sandy loam, loam, clayey loam and clay respectively. © 2018 John Wiley & Sons, Ltd.

Rainfall–runoff, flood inundation and sensitivity analysis of the 2014 Pakistan flood in the Jhelum and Chenab river basin - Muhammad Junaid Siddiqui; Sajjad Haider; H.F. Gabriel; Aamir Shahzad (Hydrological Sciences Journal, 2018)

Plant growth promoting endophytic fungi Asprgillus fumigatus TS1 and Fusarium proliferatum BRL1 produce gibberellins and regulates plant endogenous hormones - Lubna Bilal; Sajjad Asaf; Muhammad Hamayun; Humaira Gul; Amjad Iqbal; Ihsan Ullah; In-Jung Lee; Anwar Hussain (Symbiosis, 2018)

Impact of soil salinity on the microbial structure of halophyte rhizosphere microbiome - Salma Mukhtar; Babur Saeed Mirza; Samina Mehnaz; Muhammad Sajjad Mirza; Joan Mclean; Kauser Abdulla Malik (World Journal of Microbiology and Biotechnology, 2018)

Drought tolerance in citrus rootstocks is associated with better antioxidant defense mechanism - Sajjad Hussain; Muhammad Fasih Khalid; Muhammad Saqib; Shakeel Ahmad; Waseem Zafar; Muhammad Junaid Rao; Raphaël Morillon; Muhammad Akbar Anjum (Acta Physiologiae Plantarum, 2018)

Ensembling Downscaling Techniques and Multiple GCMs to Improve Climate Change Predictions in Cryosphere Scarcely-Gauged Catchment - Muhammad Azmat; Muhammad Uzair Qamar; Shakil Ahmed; Muhammad Adnan Shahid; Ejaz Hussain; Sajjad Ahmad; Rao Arsalan Khushnood (Water Resources Management, 2018)

Development of a flood forecasting system using IFAS: a case study of scarcely gauged Jhelum and Chenab river basins - Aamir Shahzad; Hamza Farooq Gabriel; Sajjad Haider; Ammara Mubeen; Muhammad Junaid Siddiqui (Arabian Journal of Geosciences, 2018)

Physiological responses of wheat to drought stress and its mitigation approaches - Zahoor Ahmad; Ejaz Ahmad Waraich; Sajjad Akhtar; Shazia Anjum; Tanveer Ahmad; Wajid Mahboob; Osama Bin Abdul Hafeez; Terence Tapera; Maryke Labuschagne; Muhammad Rizwan (Acta Physiologiae Plantarum, 2018)

Recent trends in ring opening of epoxides with sulfur nucleophiles - Sajjad Ahmad; Ameer Fawad Zahoor; Syed Ali Raza Naqvi; Muhammad Akash (Molecular Diversity, 2018)

Effects of effluent water on the abundance of cowpea insect pests - Bamphitlhi Tiroesele; Monametsi Sitwane; M. Obopile; Muhammad Irfan Ullah; Sajjad Ali (Environmental Monitoring and Assessment, 2017)

Effect of Fixed Media Surface Area on Biofouling and Nutrients Removal in Fixed Film Membrane Bioreactor Treating Sewage at Medium and High Fluxes - Muhammad Zeeshan; Sajjad Haydar; Shamas Tabraiz (Water, Air, & Soil Pollution, 2017)

Endophytes from medicinal plants and their potential for producing indole acetic acid, improving seed germination and mitigating oxidative stress - Abdul Latif Khan; Syed Abdullah Gilani; Muhammad Waqas; Khadija Al-Hosni; Salima Al-Khiziri; Yoon-Ha Kim; Liaqat Ali; Sang-Mo Kang; Sajjad Asaf; Raheem Shahzad; Javid Hussain; In-Jung Lee; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Additive effects due to biochar and endophyte application enable soybean to enhance nutrient uptake and modulate nutritional parameters - Muhammad Waqas; Yoon-Ha Kim; Abdul Latif Khan; Raheem Shahzad; Sajjad Asaf; Muhammad Hamayun; Sang-Mo Kang; Muhammad Aaqil Khan; In-Jung Lee (Journal of Zhejiang University-SCIENCE B, 2017)

Characterization of a salt resistant bacterial strain Proteus sp. NA6 capable of decolorizing reactive dyes in presence of multi-metal stress - Naila Abbas; Sabir Hussain; Farrukh Azeem; Tanvir Shahzad; Sajjad Haider Bhatti; Muhammad Imran; Zulfiqar Ahmad; Zahid Maqbool; Muhammad Abid (World Journal of Microbiology and Biotechnology, 2016)

Phenolic, flavonoid contents, anticholinesterase and antioxidant evaluation of Iris germanica var ; florentina - Farhat Ullah; Muhammad Ayaz; Abdul Sadiq; Abid Hussain; Sajjad Ahmad; Muhammad Imran; Anwar Zeb (Natural Product Research, 2016)

Spatio-temporal variations of b-value in and around north Pakistan - Khaista Rehman; Asghar Ali; Sajjad Ahmed; Wajid Ali; Aamir Ali; Muhammad Younis Khan (Journal of Earth System Science, 2015)

The Early Cambrian Khewra Sandstone, Salt Range, Pakistan: endorsing southern Indian provenance - Mubashir Jehangiri; Muhammad Hanif; Muhammad Arif; Irfan U. Jan; Sajjad Ahmad (Arabian Journal of Geosciences, 2015)

Using larger benthic foraminifera for the paleogeographic reconstruction of Neo-Tethys during Paleogene - Sajjad Ahmad; Wahid Jalal; Fahad Ali; Muhammad Hanif; Zaheen Ullah; Suleman Khan; Asghar Ali; Irfan U. Jan; Khaista Rehman (Arabian Journal of Geosciences, 2015)

mRNA secondary structure engineering of Thermobifida fusca endoglucanase (Cel6A) for enhanced expression in Escherichia coli - Imran Ali; Rehana Asghar; Sajjad Ahmed; Muhammad Sajjad; Muhammad Tariq; M. Waheed Akhtar (World Journal of Microbiology and Biotechnology, 2015)

Environment and air pollution: health services bequeath to grotesque menace - Muhammad Imran Qureshi; Amran Md. Rasli; Usama Awan; Jian Ma; Ghulam Ali; Faridullah; Arif Alam; Faiza Sajjad; Khalid Zaman (Environmental Science and Pollution Research, 2015)

Genetic diversity revealed by physiological behavior of citrus genotypes subjected to salt stress - Sajjad Hussain; Raphaël Morillon; Muhammad Akbar Anjum; Patrick Ollitrault; Gilles Costantino; François Luro (Acta Physiologiae Plantarum, 2015)

Erratum to: The inner ramp facies of the Thanetian Lockhart Formation, western Salt Range, Indus Basin, Pakistan - Muhammad Hanif; Muhammad Imraz; Fahad Ali; Muhammad Haneef; Abdus Saboor; Shahid Iqbal; Sajjad Ahmad (Arabian Journal of Geosciences, 2014)

The inner ramp facies of the Thanetian Lockhart Formation, western Salt Range, Indus Basin, Pakistan - Muhammad Hanif; Muhammad Imraz; Fahad Ali; Muhammad Haneef; Abdus Saboor; Shahid Iqbal; Sajjad Ahmad (Arabian Journal of Geosciences, 2014)

The challenges of reducing greenhouse gas emissions and air pollution through energy sources: evidence from a panel of developed countries - Ghulam Akhmat; Khalid Zaman; Tan Shukui; Faiza Sajjad; Muhammad Azhar Khan; Muhammad Zahir Khan (Environmental Science and Pollution Research, 2014)

Directed Evolution of Clostridium phytofermentans Glycoside Hydrolase Family 9 Endoglucanase for Enhanced Specific Activity on Solid Cellulosic Substrate - Sajjad Ahmad; Hui Ma; Muhammad Waheed Akhtar; Yi-Heng Percival Zhang; Xiao-Zhou Zhang (BioEnergy Research, 2014)

2,5-Disubstituted-1,3,4-oxadiazoles: thymidine phosphorylase inhibitors - Khalid Mohammed Khan; Mubeen Rani; Nida Ambreen; Muhammad Ali; Sajjad Hussain; Shahnaz Perveen; Muhammad Iqbal Choudhary (Medicinal Chemistry Research, 2013)

Prospects of raising Sahiwal cow calves for veal production under tropical environment - Shaukat Ali Bhatti; Kamran Nazir; Muhammad Jamil Basra; Muhammad Sajjad Khan; Muhammad Sarwar; Muhammad Ashraf Iqbal Mughal (Tropical Animal Health and Production, 2013)

The low down on association mapping in hexaploid wheat (Triticum aestivum L.) - Muhammad Sajjad; Sultan Habibullah Khan; Abdul Mujeeb Kazi (Journal of Crop Science and Biotechnology, 2012)

Monitoring of cotton dust and health risk assessment in small-scale weaving industry - Muhammad Wajid Tahir; Muhammad Waseem Mumtaz; Shanza Tauseef; Muqadas Sajjad; Awais Nazeer; Nazish Farheen; Muddsar Iqbal (Environmental Monitoring and Assessment, 2012)

Effect of diet on preweaning performance of Sahiwal calves - Shaukat Ali Bhatti; Muhammad Faisal Ahmed; Peter Charles Wynn; David McGill; Muhammad Sarwar; Muhammd Afzal; Ehsan Ullah; Musarrat Abbas Khan; Muhammad Sajjad Khan; Russell Bush; Hassan Mahmood Warriach; Ahrar Khan (Tropical Animal Health and Production, 2012)

Erratum to: Caprine pleuropneumonia in Beetal goats - Riaz Hussain; Muhammad Auon; Ahrar Khan; Muhammad Zargham Khan; Fazal Mahmood; Sajjad Ur-Rehman (Tropical Animal Health and Production, 2012)

Contagious caprine pleuropneumonia in Beetal goats - Riaz Hussain; Muhammad Auon; Ahrar Khan; Muhammad Zargham Khan; Fazal Mahmood; Sajjad Ur-Rehman (Tropical Animal Health and Production, 2012)

Comparative effectiveness of Pseudomonas and Serratia sp. containing ACC-deaminase for coinoculation with Rhizobium leguminosarum to improve growth, nodulation, and yield of lentil - Zahir Ahmad Zahir; Muhammad Zafar-ul-Hye; Saima Sajjad; Muhammad Naveed (Biology and Fertility of Soils, 2011)

Estimation of a Unique Pair of Nash Model Parameters: An Optimization Approach - Muhammad Masood Ahmad; Abdul Razzaq Ghumman; Sajjad Ahmad; Hashim Nisar Hashmi (Water Resources Management, 2010)

Estimation of Clark’s Instantaneous Unit Hydrograph Parameters and Development of Direct Surface Runoff Hydrograph - Muhammad Masood Ahmad; Abdul Razzaq Ghumman; Sajjad Ahmad (Water Resources Management, 2009)

The detection of antibody against peste des petits ruminants virus in Sheep, Goats, Cattle and Buffaloes - Haider Ali Khan; Muhammad Siddique; Sajjad-ur-Rahman; Muhammad Abubakar; Muhammad Ashraf (Tropical Animal Health and Production, 2008)